Core genome analysis reveals novel drug and vaccine targets in multidrug-resistant Citrobacter koseri - Zubda Ashraf; Fizza Arshad; Samina N. Shakeel; Faiz Ur Rahman; Khaled Fahmi Fawy; Sarah A. Altwaim; Saeed M. Alasmari; Abid Ali; Muhammad Umer Khan; Mohibullah Shah (Molecular Genetics and Genomics, 2026)

Hydrodynamic response and tendon mechanics of tension-leg platform floating offshore wind turbines: A critical review and future perspectives - Haozhe Bai; Sami Ur Rehman; Abid Ali; Muhammad Irslan Khalid; Wei Shi; Fengmei Jing; Sajid Ali; Muhammad Asghar; Sheraz Hussain; Chunlei He (Ocean Engineering, 2026)

Comparative study on the implementation of Custom Convolutional Neural Networks (CNNs), MobileNet V3 and ResNet-50 architecture for defect detection in Carbon Fiber Reinforced Plastics (CFRPs) - Hussnain Abid; Muhammad Daniyal Hassan; Saad Nauman (Next Research, 2026)

Advanced Modeling and Decision Support for Anti-Allergic Drugs Using Topological Indices and QSPR Analysis - Muhammad Waheed Rasheed; Abid Mahboob; Asima Parveen; Mona Bin-Asfour (Journal of Pharmaceutical Innovation, 2026)

Microplastics in Urban Wastewater: A Vector for Chemical and Biological Pollutants with Emerging Health Risks - Mamoona Sadia; Abid Mahmood; Muhammad Ibrahim; Bilal Aslam (Environmental Research, 2026)

Comparative Analysis of Multidrug Resistance and Virulence in Interconnected Clinical and Environmental Salmonella Strains from Karachi, Pakistan - Yamina Usmani; Rabia Ilyas; Sidrah Asghar; Moatter Zehra; Zulfiqar Ali Mirani; Rao Muhammad Abid Khan; Shabana Usman Simjee; Ayaz Ahmed (Current Microbiology, 2026)

Synergistic role of biochar, AMF, and PGPR in enhancing drought tolerance and productivity of wheat (Triticum aestivum L.) - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Islem Abid; Awais Ahmad; Vusala Ismayilova; Manal Abdulaziz Binobead; Rashid Iqbal (Cereal Research Communications, 2026)

Early winter precipitation variability over Pakistan and associated ENSO teleconnections - Romesa Najeeb; Irfan Ur Rashid; Rehan Ahmed; Muhammad Adnan Abid; Elham Ghasemifar; Ibrahim Alsafari (Theoretical and Applied Climatology, 2026)

Visual analytics of vaccine hesitancy: mapping sentiment and misinformation flows across digital ecosystems - Shahbaz Aslam; Sobia Abid; Arshad Ali; Babar Hussain; Muhammad Zahid Bilal (Next Research, 2026)

The role of financial inclusion, social equity, and technological innovation to promote inclusive wealth: Empirical evidence from selected G 20 countries - Sohail Abbas; Shazia Kousar; Farwa Jabbir; Muhammad Afzal; Aena Abid; Heli Lu (Journal of Environmental Management, 2026)

Fabrication of Magnetic Polyvinyl Alcohol and Polyvinyl Pyrrolidone Ferrite Nanocomposites for the Removal of Reactive Dyes from wastewater by Adsorption Process - Muhammad Hasnain; Abdul Qadir Ahmad; Muhammad Junaid; Anam Zulfiqar; Rizwan Ali; Hafiz Muhammad Waqar Abid; Rajesh Kumar Manavalan; Khalid Bilal; Mahmoud F. Y. Shalaby (Water, Air, & Soil Pollution, 2026)

Infectious clone–based dissection of delayed pathogenicity and evolutionary dynamics of Papaya leaf curl Guangdong virus (PaLCuGdV) - Renshu Huang; Muhammad Arif; Amna Saeed; Cheng Song; Omer Beyhan; Muhammed Said Yolcu; Islem Abid (European Journal of Plant Pathology, 2026)
Papaya leaf curl Guangdong virus (PaLCuGdV) is an economically significant begomovirus, although its pathogenicity and evolutionary dynamics are poorly understood. This study involved the construction of a full infectious clone of PaLCuGdV, which was agroinoculated into Nicotiana benthamiana ( N. benthamiana ) to assess the infectivity and symptomatology. The infectious clone elicited typical begomoviral symptoms just at 28 days post-inoculation, signifying delayed pathogenicity. Infection efficiency varied with strain, with successful transmission achieved using Agrobacterium GV301, but not with EHA105 alone. Southern blot analysis confirmed active viral DNA replication solely in diseased plants. Comparative sequencing and recombination analysis identified numerous recombination events among worldwide PaLCuGdV isolates, with the newly defined strain serving as a primary recombinant progenitor. These findings indicate that PaLCuGdV displays delayed symptom expression, strain-specific infectivity, and evolutionary diversity driven by recombination, underscoring the value of infectious clone systems for functional and evolutionary studies of begomoviruses.

Discovery and Functional Evaluation of Enterobacter gossypi sp. nov. (RT) for Salinity Stress Alleviation in Cotton - Abid Ullah; Aqsa Bibi; Ma Yonghui; Muhammad Atif Azeem; Ali Hazrat; Yasir Arafat; Caixia Han; Nigora Kuchkarova; Hua Shao (Journal of Soil Science and Plant Nutrition, 2026)

Integrated BIM-GIS and finite element-based framework for building planning and design - Aaqib Najeeb; Zili Zhang; Muhammad Arsalan Khan; Kong Fah Tee; Taimoor Shehzad; Abid Ali Shah; Zeshan Alam (Innovative Infrastructure Solutions, 2026)

AcrAB-NodT overexpression drives envelope destabilization and metal sensitivity in Caulobacter vibrioides - Muhammad Shahid Mehmood; Yohana Amos; Muhammad Ali Abid; Ali Shan Hafeez; Naseeb Danaf (Archives of Microbiology, 2026)

Recent advances in structural damage assessment methods for ship collisions: A critical review of experimental, numerical, and analytical approaches - Abid Paripurna Fuadi; Muhammad Arif Budiyanto; Sunaryo; Achmad Riadi; Teguh Muttaqie; Xueqian Zhou (Ocean Engineering, 2026)

Acacia (Acacia nilotica) seed oil-based nanoemulsion delays softening of mango fruit by modulating oxidative stress and suppressing cell wall degradation - Shaghef Ejaz; Abdul Manan Abbas; Sajid Ali; Muhammad Azam; Mehdi Maqbool; Muhammad Saqib; Muhammad Abid (Journal of Stored Products Research, 2026)

Statistical optimization of exopolysaccharides by indigenously isolated Lactobacillus strain under submerged fermentation - Madah Zahra Awan; Fouzia Tabssum; Muhammad Nadeem; Najeeb Ullah; Abid Sarwar; Neha Mazhar; Tariq Aziz; Ashwag Shami; Hanan Abdulrahman Sagini; Saleh A. Alsanie; Nouf Abdullah Alharbi; Mansour Albalji (World Journal of Microbiology and Biotechnology, 2026)

Algorithmic insights: How FDI sources, digital financial inclusion, and geopolitics collide in Pakistan's environmental landscape - Abid Ali Randhawa; Muhammad Shahbaz; Zokir Mamadiyarov (Journal of Environmental Management, 2026)

Bacterial Metabolite-Derived NDM-1 Inhibitors: A Computational Strategy to Overcome β-Lactam Resistance - Bader S. Alotaibi; Farhat Shabbir; Muhammad Umer Khan; Iqra Ahmad; Hira Khalid; Shahid Aziz; Abid Ali; Sonia Younas; Hanna Dib; Khaled Fahmi Fawy; Umar Nishan; Mohibullah Shah (Probiotics and Antimicrobial Proteins, 2026)

Retraction Note: Salinity effects on growth, biomass production, and genetic resources for phytoremediation potential of halophyte species in the desert - Muhammad Abid; Muhammad Rafay; Tanveer Hussain; Muhammad Azeem Sabir; Muneeb Khalid; Muhammad Madnee; Hussain Ahmed Makki; Muhammad Qasim; Ehab I. Taha; Mounir M. Bekhit; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

mcr gene family evolution and structural mechanisms of colistin resistance: from mcr-1 to emerging variants - Muhammad Shahid Mehmood; Uthpala Kavindi Rupasinghe Koggala Marakkalage; Tabish Arif; Fariha Javaid; Muhammad Ali Abid; Muntha Shahid; Anwar Parvez; Muhammad Nabeel Saddique; Sultan Ali (Archives of Microbiology, 2026)

Advanced fabrication strategies for Durable, High-Efficiency, and scalable solid oxide fuel cells - Abid Ullah; Shahbaz Ahmad; Tahir Ali; Ayesha Samreen; Saim Saher; Muhammad Zulqarnain Arif; Arunachala M. Kannan (Fuel, 2026)

Interactions and binding mechanisms of soy protein isolate with theasinensin A in different pH conditions by multi-spectroscopy analysis and molecular docking - Haoyu Zhang; Weiqi Xu; Yulu Wang; Xia Fan; Qiankun Guo; Hongjun Liu; Jialu Ao; Tianjin Sun; Muhammad Abid; Xiaoxiong Zeng (Food Chemistry, 2026)

Bio-inspired ZIF-derived Co/N-doped carbon for efficient one-step CO2 mineralization under ambient conditions - Hafiz Muhammad Waqar Abid; Meiirzhan Nurmyrza; Woojin Lee; Mannix P. Balanay (Chemical Engineering Journal, 2026)

Synergistic nanobioremediation: exploring nanoparticle–plant–microbe interactions for sustainable soil decontamination - Abid Hussain; Muhammad Kabir (Nanotechnology for Environmental Engineering, 2026)

Integrating phenotypic, antioxidant, and molecular analyses to identify drought-tolerant wheat genotypes for climate resilience and genetic improvement - Hafiz Ghulam Muhu Din Ahmed; Tao Yang; Mueen Alam Khan; Muhammad Irfan Akram; Rashid Iqbal; Sajid Hussain; Muhammad Danial Shafiq; Mohamed El-Zaidy; Islem Abid (Cereal Research Communications, 2026)

Sublethal effects of azadirachtin on life table parameters of Musca domestica (Diptera: Muscidae): implications for population dynamics in Pakistan - Naeem Iqbal; Nauman Sadiq; Hafiz Azhar Ali Khan; Allah Ditta Abid; Muhammad Sohail Shahzad; Muhammad Nadir Naqqash; Adnan Akhter (International Journal of Tropical Insect Science, 2026)

Species-driven variability in soil health and carbon storage across bamboo plantations - Ghulam Yasin; Syed Amir Manzoor; Muhammad Farooq Azhar; Muhammad Talha Imtiaz; Shafeeq Ur Rahman; Islem Abid; Manal Abdulaziz Binobead; Rashid Iqbal (Environmental Monitoring and Assessment, 2026)

Modeling the interplay of cultivars, irrigation regimes, and planting dates for optimizing cotton productivity in core and non-core cotton areas of Pakistan - Raheel Osman; Muhammad Shahid Iqbal; Zareen Sarfraz; Abid Mahmood; Muhammad Rafiq Shahid; Til Feike; Lin Wang; Shenglei Fu; Syed Tahir Ata-Ul-Karim (Computers and Electronics in Agriculture, 2026)

Intraspecific and interspecific variation of Salvadora species (S. oleoides Decne. and S. persica L.) along an aridity gradient in dryland ecosystems - Ummar Iqbal; Atta Hussain Sahir; Muhammad Sharif; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf; Sadaf Rafiq; Sana Abid (Trees, 2026)

Microstructural adaptations of snow bush (Aerva javanica (Burm.f.) Juss. Ex Schult.) in desert ecosystems - Sana Abid; Ummar Iqbal; Muhammad Sharif; Sadaf Rafiq; Aisha Sana; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf (The Science of Nature, 2026)

Anti-arthritic and anti-inflammatory effects of BMZD-2CPE in a CFA and carrageenan-induced animal model - Samiullah Wazir; Farah Abid; Aisha Mobashar; Arham Shabbir; Muhammad Awais; Humaira Nadeem; Hafiz Aamir Ali Kharl; Esmael M. Alyami; Amir Bouallegue; Norah Hamdi; Mohammed Bourhia; Abdullah R. Alanzi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Aflatoxin surveillance in Punjab’s dairy sector: feed and milk contamination - Naveed Akbar; Farhan Saeed; Muhammad Atif Randhawa; Sanaullah Iqbal; Asif Meraj; Abhayveer Singh; Bushra Niaz; T. Krithiga; Rajashree Panigrahi; Amara Rasheed; Zunaira Basharat; Muhammad Afzaal; et al. (Mycotoxin Research, 2026)

Development of a Parametric Multi-Material Physics-Informed Neural Network for real-time heat transfer prediction in spherical tokamak divertor under transient heat loads - Habib Ur Rahman; Abid Hussain; Muhammad Ilyas; Lei Li; Khalid Waheed; Manzoor Ahmed (Annals of Nuclear Energy, 2026)

Truncated Variants in FAM20A and WDR72 Genes Underlie Autosomal Recessive Amelogenesis Imperfecta in Four Pakistani Families - Sadaqat Ullah; Sher Alam Khan; Samin Jan; Salah Ud Din; Nazif Muhammad; Zia Ur Rehman; Abid Jan; Muhammad Tariq; Noor Muhammad; Abdul Ghani; Naveed Wasif; Saadullah Khan (Biochemical Genetics, 2026)
Amelogenesis Imperfecta (AI) is a set of hereditary diseases affecting enamel development, leading to various types of enamel defects, potentially impacting oral health unassociated with other generalized defects. AI manifests in syndromic and non-syndromic forms and can be inherited through autosomal recessive, autosomal dominant, or X-linked inheritance patterns. Genetic studies have identified sequence variants in a number of genes (≥ 70) linked to both syndromic and non-syndromic AI, highlighting the genetic diversity underlying the condition. The current study involved clinical evaluation and exome sequencing, aimed at identifying the causative variants in four unrelated consanguineous Pakistani families presenting AI phenotypes. The exome sequencing results revealed a novel homozygous frameshift variant FAM20A : NM_017565.4, c.188dupA; p.(Asp63Glufs*17) in families A, B, and C while a nonsense homozygous variant WDR72 : NM_182758.4, c.2686C > T; p. (Arg896*) in family D. The segregation of both variants was confirmed by Sanger sequencing. Bioinformatics analysis predicted the pathogenicity of these genetic variants. These alterations suggest functional consequences, potentially impairing the FAM20A and WDR72 proteins and causing dental anomalies. This investigation significantly broadens our understanding of FAM20A and WDR72 ’s involvement in AI. Furthermore, this study highlights the genetic heterogeneity of AI (involving FAM20A and WDR72 in this study) within the Pakistani population.

Probiotic-based mycotoxin detoxification in poultry feed: mechanisms, efficacy, challenges, and future directions for sustainable production - Noor Muhammad; Iram Liaqat; Sajida Naseem; Fakhar-un Nisa Yunus; Abid Ali (Archives of Microbiology, 2026)

Assessing Spatiotemporal Variability in Soil Moisture under a Changing Climate Using Hydrological Models in Hilly Landscapes - Muhammad Waseem Rasheed; Junfang Cui; Jialiang Tang; Abid Sarwar; Mostafa Moradzadeh; Muhammad Faheem (Water Resources Management, 2026)

Genetic and morphological data indicate the occurrence of a Rhipicephalus sp. and the absence of Rhipicephalus linnaei in Pakistan - Muhammad Numan; Zaibullah Khan; Sher Bahadar Khan; Mohibullah Shah; Iram Liaqat; Itabajara da Silva Vaz Junior; Lidia Chitimia-Dobler; Abid Ali; Zhihua Sun; Mashal M. Almutairi (Tropical Animal Health and Production, 2026)

Microbial Dream Team: Cotton Performs Better in Salty Soil with Pseudomonas hunanensis RT-12 and Staphylococcus caprae DS-2 - Abid Ullah; Sajjad Ahmad; Muhammad Atif Azeem; Shariat Ullah; Sami Ullah; Muhammad Laiq; Asma Shah; Hua Shao (Current Microbiology, 2026)

An Adaptive Nudging Scheme with Spatially Varying Gain for Improving the Ability of Ocean Temperature Assimilation in SPEEDY-NEMO - Yushan Wang; Fei Zheng; Changxiang Yan; Muhammad Adnan Abid (Journal of Marine Science and Engineering, 2025)
Nudging remains a cost-effective data assimilation technique in coupled climate models, yet conventional schemes with fixed spatial strengths struggle to represent heterogeneous ocean processes. This study introduces an adaptive nudging framework in which a spatially varying gain matrix dynamically balances model and observational errors, providing a more physically consistent determination of nudging coefficients. Implemented in the SPEEDY-NEMO coupled model, the method is systematically evaluated against a traditional latitude-dependent scheme. Results show substantial improvements in subsurface temperature assimilation across key regions, including the Niño3.4, tropical Indian Ocean, North Pacific, North Atlantic, and northeastern Pacific. The most pronounced gains occur above and within the thermocline, where strong stratification renders fixed nudging strengths inadequate, yielding a 20–30% reduction in RMSE and a 30–50% increase in correlation. In mid- to high-latitude regions, improvements extend to greater depths, consistent with deeper thermocline structures. The adaptive framework corrects both systematic bias and variance, enhancing not only the mean state but also variability representation. Additional benefits are found in salinity, currents, and sea surface height, demonstrating that spatially adaptive nudging provides a more effective and practical alternative for improving ocean state estimation in coupled models.

Phenotypic Characterization and Adaptability of Wild Sugarcane to Diverse Pedospheric and Atmospheric Conditions - Ummar Iqbal; Mehboob Ahmad; Muhammad Sharif; Abdul Wahab; Muhammad Yousuf; Sadaf Rafiq; Sana Abid (Tropical Plant Biology, 2025)

Runoff prediction under climatic variability using SWAT and machine learning models: a case study of the Hunza River basin - Muhammad Ghawas Kareem; Deshan Tang; Muhammad Farhan; Anis Ur Rehman Khalil; Hafiz Ahmad Hammad Abid (Theoretical and Applied Climatology, 2025)

Functional insights into drought-tolerant PGPR: impacts on physiological responses and yield performance of direct-seeded rice under water stress - Faiza Javed; Sumera Iqbal; Muhammad Shahbaz Farooq; Khajista Jabeen; Noshin Ilyas; Abid Majeed (The Science of Nature, 2025)

Identification of a biallelic MMUT variant (p.Thr230Arg) and its global perspective on clinical management - Sumreena Mansoor; Qamar Ali; Sabeen Abid Khan; Munir Iqbal Malik; Muhammad Imran; Raheel Qamar; Maleeha Azam (Molecular Biology Reports, 2025)

Computational identification of membrane proteins for vaccine design against drug-resistant Moraxella catarrhalis - Fizza Arshad; Rania Pervaiz; Asifa Sarfraz; Hasan Ejaz; Amal Alotaibi; Riaz Ullah; Umar Nishan; Abid Ali; Muhammad Umer Khan; Mohibullah Shah (Molecular Genetics and Genomics, 2025)

Evaluating Soil Reclamation and Growth Enhancing Potential of Various Types of Biochar with Respect To Rice Crop Cultivated in Saline Sodic Soil - Imran Shehzad; Ghulam Sarwar; Abid Mahmood; Kashf Mehmood; Zuhair Hasnain; Muhammad Zeeshan Manzoor; Danish Ibrar; Saqib Bashir; Manzer H. Siddiqui; Saud Alamri; Shahbaz Khan (Journal of Soil Science and Plant Nutrition, 2025)

Interleukin-37 modulates microglial phenotype and inhibits inflammatory response via the MyD88/NF-κB pathway in lipopolysaccharide-induced neuroinflammation - Jingwen Zhang; Muhammad Abid Hayat; Yu Si; Tao Guo; Yinying Ni; Qian Wang; Yancheng Hong; Yudie Cao; Sijia He; Zijuan Weng; Fengmei Li; Hao Zuo; et al. (Inflammation Research, 2025)

Stratigraphic Forward Modeling of Late Quaternary Fluvial Dynamics in the Indus River Delta, Pakistan: Insights into Sea Level-Driven Sedimentary Evolution - Hafiz Ahmed Raza Hassan; Keyu Liu; Jianliang Liu; Muhammad Jawad Munawar; Saif Ur Rehman; Abid Hussain (Journal of Ocean University of China, 2025)

Environmental extremes in cholistan rangeland ecosystem: effects on floral diversity, rangeland productivity, and carrying capacity - Muhammad Abid; Muhammad Rafay; Muneeb Khalid; Muhammad Umair Riaz (Brazilian Journal of Botany, 2025)

Protective biological control of chickpea blight disease by enhancing plant immunity through seed priming and foliar spraying with Cuminum cyminum essential oil - Hafiz Muhammad Saqib; Sobia Chohan; Muhammad Abid (Journal of Plant Pathology, 2025)

Seismic fragility and resilience assessment of pile-supported wharves with isolation systems in liquefied soil - Yao Cui; Sami Ur Rehman; Zhuoxin Wang; Ying Cui; Abid Ali; Muhammad Shameer Faisal (Ocean Engineering, 2025)

Multivalent metal-ions intercalation for enhanced structural stability and pseudocapacitance in titanium carbonitride (Ti₃CNTₓ) MXenes for asymmetric supercapacitor applications - Sheryar Abid; Aiza Kanwal; Muhammad Zubair Iqbal; Muhammad Yousaf; Asif Mahmood; Syed Rizwan (Chemical Engineering Journal, 2025)

Risk assessment of synthetic insecticides and botanicals to Western honey bee, Apis mellifera (Hymenoptera: Apidae) - Sami Ullah; Naeem Iqbal; Muhammad Sohail Shahzad; Hafiz Azhar Ali Khan; Khalid Rafiq; Allah Ditta Abid; Mudssar Ali; Shafqat Saeed (International Journal of Tropical Insect Science, 2025)

Silicic acid seed pre-treatment modulates growth and antioxidant responses in maize under drought stress - Abid Ali; Sara Zafar; Kashf Mehmood; Zuhair Hasnain; Muhammad Nawaz; Syed Muhammad Junaid Jalal Gilani; Manzer H. Siddiqui; Saud Alamri; Shahbaz Khan (The Science of Nature, 2025)

From scorching sands to survival: adaptive tale of the genus Tribulus (T. longipetalus, T. terrestris and T. pentandrus) in desert ecosystem - Ummar Iqbal; Muhammad Sharif; Sana Abid; Sadaf Rafiq; Abdul Wahab (The Science of Nature, 2025)

Low-Level Arsenic Removal from Drinking and Wastewater Using La@MOF-808 in Lahore, Pakistan - Hassan Nawaz; Muhammad Ibrahim; Hirra Anjum; Abid Mahmood; David V. P. Sanchez (International Journal of Environmental Research, 2025)

Thermal Thresholds and Mechanical Behavior of Granitic Rocks from Northern Pakistan: Implications for Rock Engineering - Abdul Rahim Asif; Muhammad Sajid; Waqas Ahmed; Ihtisham Islam; Abid Nawaz; Salman Ahmed Khattak (Geotechnical and Geological Engineering, 2025)

Bay leaves: the neuroprotective dietary spice via inhibition of amyloid-like aggregation - Nazish Mustafa; Sana Khan; Laila Anwar; Mir Muhammad Uzairullah; Huma Aslam Bhatti; Syed Abid Ali; Ghulam Abbas (Metabolic Brain Disease, 2025)

Variations in the compositional profile of polycyclic aromatic moieties in coals from Bara, Patala and Salt Range formations: Insights into the mechanisms affecting the sedimentary record - Arif Nazir; Qaiser Hussain; Saeed Abbas; Fraz Khalid; Muhammad Deen; Abid Ali; Munawar Iqbal (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Isolation, Identification, biochemical and molecular characterization of potential source of enterotoxigenic strains of Staphylococcus aureus from the bovine raw and mastitis milk - Sikander Ali; Farzana Nazir; Muhammad Usman Ahmad; Hira Sarfraz; Abid Sarwar; Tariq Aziz; Ashwag Shami; Fahad Al-Asmari; Areej A. Alhhazmi; Abeer M. Alghamdi; Fakhria A. Al-Joufi (International Dairy Journal, 2025)

Spatial distribution of mangrove soil organic carbon in Indus Delta, Pakistan: A multi-sensor remote sensing and machine learning approach - Hammad Gilani; Muddasir Shah; Shahzada Sohail Ijaz; Muhammad Asif; Abid Nazir; Niall P. Hanan (Estuarine, Coastal and Shelf Science, 2025)

Genetic Variability Among Isolates of Curvularia lunata and Exserohilum rostratum Causing Brown Leaf Spot of Rice from Pakistan - Muhammad Faizan Anwar Khan; Abid Riaz; Rafia Ahsan; Ishaq Ahmad; Saif Ullah; Ahmed Raza; Muhammad Zakria (Current Microbiology, 2025)

Innovative Nanotechnology and Molecular Probes for Real-time Monitoring and Therapeutic Modulation of Pyroptosis in Cancer and Inflammatory Diseases - Wajahat Ali; Zainab Saba; Muhammad Saqib; Shabana Batool; Awais; Fatima Rahman; Ali Asgher Shuja; Junaid Abid; Seema Batool; Kulsoom; Mukhayya Ruzieva; Murodjon Yaxshimuratov; et al. (Cell Biochemistry and Biophysics, 2025)

Harnessing Cuminum cyminum L. (cumin) essential oil as a promising biocontrol agent against Ascochyta rabiei: Insights from screening and in planta evaluation - Hafiz Muhammad Saqib; Sobia Chohan; Muhammad Azeem; Muhammad Farhan Ul Haque; Muhammad Abid (South African Journal of Botany, 2025)

Intensifying the charge transfer on N–(CxNx+1) catalysts system: A cutting–edge approach for sunlight driven hydrogen production† - Ejaz Hussain; Muhammad Jalil; Javeria Mansab; Muhammad Zeeshan Abid; Shahid Iqbal; Abeer Hashem; Amal M. Al-Mohaimeed; Elsayed Fathi Abd_Allah; Khezina Rafiq (Fuel, 2025)

Investigation of the genesis and intensification of simultaneous cyclones in the Arabian sea and Bay of Bengal in November 2020 - Abhishek Kumar; Arun Chakraborty; Mansour Almazroui; Muhammad Mubashar Dogar; Irfan Ur Rashid; Muhammad Adnan Abid; Moetasim Ashfaq (Theoretical and Applied Climatology, 2025)

Genotypic Profiling, Functional Analysis, Cholesterol-Lowering Ability, and Angiotensin I-Converting Enzyme (ACE) Inhibitory Activity of Probiotic Lactiplantibacillus plantarum K25 via Different Approaches - Tariq Aziz; Hu Hangyu; Muhammad Naveed; Muhammad Aqib Shabbir; Abid Sarwar; Jasra Nasbeeb; Yang Zhennai; Metab Alharbi (Probiotics and Antimicrobial Proteins, 2025)

Asteraceae in Pakistan and Kashmir with special emphasis on distribution pattern and endemism - Muhammad Qaiser; Anjum Perveen; Jan Alam; Haidar Ali; Roohi Abid (Genetic Resources and Crop Evolution, 2025)

Revealing Lactiplantibacillus Plantarum K25 Derived (Z)-18-Octadec-9-Enolide in Modulating Aquaporin-8 in Colorectal Cancer by Bridging the Gut Microbiome and Membrane Biology - Tariq Aziz; Muhammad Aqib Shabbir; Abid Sarwar; Zhennai Yang; Lin Lin; Wafa Abdullah I. Al-Megrin; Ashwag Shami; Maher S. Alwethaynani; Areej A Alhhazmi; Fahad Al-Asmari; Fakhria A. Al-Joufi; Deema Fallatah (Cell Biochemistry and Biophysics, 2025)

Selecting the best CMIP6 GCMs for application and downscaling studies over Pakistan, Nepal and Bangladesh - Shaukat Ali; Michelle Simões Reboita; Zulfiqar A. Bhutta; Muhammad Arif Goheer; Joao Gabriel Martins Ribeiro; Christie André de Souza; Glauber Willian Ferreira; Jai Das; Rida S. Kiani; Azfar Hussain; Fatima Saeed; Muhammad Adnan Abid; et al. (Acta Geophysica, 2025)

Structural Traits Driving Water Hyacinth (Eichhornia crassipes) Aggressive Spread and Ecosystem Disruption - Ummar Iqbal; Abdul Wahab; Sadaf Rafiq; Sibgha Noreen; Sana Abid; Muhammad Sharif; Mehboob Ahmad; Muhammad Yousuf (Water, Air, & Soil Pollution, 2025)

Enhanced apoptosis in damaged laminar tissue of acute laminitis induced by oligofructose overload in dairy cows - Muhammad Abid Hayat; Jiafeng Ding; Xianhao Zhang; Tao Liu; Jiantao Zhang; Hong Bin Wang (Veterinary Immunology and Immunopathology, 2025)

Development and techno-economic analysis of an innovative solar-based ammonia synthesis system - Zihan Lin; Muhammad Sajid Khan; Saboora Khatoon; Shuiqing Zhou; Weiya Jin; Muhammad Abid; Syed Waqas Hussain Shah; Chen Chen; Ali Ahmed Alqahtani (Process Safety and Environmental Protection, 2025)

Epidemiology and genetic characterization of Alternaria alternata causing leaf spot in Fragaria × ananassa - Nasir Mehmood; Abid Riaz; Salman Ghuffar; Sadaf Anwaar; Nyla Jabeen; Isha Shaheen; Muhammad Qasim; Salma Saeed Khan; Muhammad Rauf; Tauseef Anwar; Huma Qureshi; Ghadah Salim Abusalim; et al. (Fungal Biology, 2025)

Combined Application of Plant Growth Promoting Rhizobacteria and Kinetin on Maize Growth, Chlorophyll, Osmoregulation, and Oxidative Metabolism Under Drought Stress - Rubaika Khurshid; Shagufta Perveen; Muhammad Bilal Hafeez; Abid Niaz; Saeedeh Zarbakhsh (Journal of Soil Science and Plant Nutrition, 2025)

Genome-wide identification and characterization of light-responsive FAR1 gene family in finger millet (Eleusine coracana) under abiotic stress - Urooba Abid; Azhar Iqbal; Mahnoor Mazher; Shabana Bibi; Sara Ashraf; Mohamed Kamel; Ghadeer M. Albadrani; Muath Q. Al-Ghadi; Mohamed M. Abdel-Daim; Muhammad Sajid (Genetic Resources and Crop Evolution, 2025)

Exploring the morpho-physiological responses of maize to nickel stress modulated by salicylic acid - Atifa Masood; Sumaira Arooj; Muhammad Shahbaz; Noreen Khalid; Muhammad Sajjad; Muhammad Faisal Maqsood; Sunbal Khalil Chaudhari; Abida Abid; Rafia Zainab; Noor Fatima (Cereal Research Communications, 2025)

Impact of petrographic and physico-mechanical properties on aggregate suitability of the early Devonian Nowshera formation: a case study from the Peshawar Basin, Pakistan - Abid Nawaz; Muhammad Sajid; Waqas Ahmed; Abdul Rahim Asif; Muhammad Ishaq (Carbonates and Evaporites, 2025)

Evidencing the socioeconomic impact of agroforestry in an arid climate: a case study of district Bahawalpur, Punjab, Pakistan - Muhammad Madnee; Tanveer Hussain; Muhammad Abid; Muneeb Khalid; Hussain Ahmed Makki; Nugraha Akbar Nurrochmat; Mahmuod Abubakar Bashir (Agroforestry Systems, 2025)

Comparative efficacy of Cymbopogon winterianus essential oil and nanoemulsion as a sustainable biopesticide to control Tribolium castaneum: Effect on biomolecules of insect and seed germination - Tanzeela Riaz; Sana Abid; Muhammad Afzal; Farah Rauf Shakoori (Journal of Stored Products Research, 2025)

Interactive effects of soil moisture and temperature on chromium-induced microbial and enzymatic stress - Idrees Haider; Muhammad Arif Ali; Muhammad Sanaullah; Muhammad Taimoor Shakeel; Syed Atif Hasan Naqvi; Muhammad Akmal; Muhammad Abid Ali Khan; Muhammad Umer Iqbal; Niaz Ahmad; Mahmoud Moustafa; Mohammed O. Alshaharni; Uthman Algopishi (World Journal of Microbiology and Biotechnology, 2025)

Assessing the impact of air pollution on global and diffuse solar radiation in Karachi, Pakistan: a comparative analysis of multiple linear regression and artificial neural network models - Muhammad Uzair Yousuf; Abid Ali; Muhammad Umair (Theoretical and Applied Climatology, 2025)

Synthesis, hydrolysis, and COX-2/15-LOX inhibitory evaluation of 4-Acetamidophenyl 4-Bromobenzoates - Uzma Afzal; Abid Mahmood; Muhammad Zubair; Nasir Rasool; Aqsa Kanwal; Maria Sohail; Gulraiz Ahmad (Medicinal Chemistry Research, 2025)

ENSO teleconnections and predictability of the boreal summer temperature over the Arabian Peninsula in C3S and Saudi-KAU seasonal forecast systems - Mansour Almazroui; M. Salman Khalid; Muhammad Adnan Abid; Irfan Ur Rashid; Shahzad Kamil; Haroon Siddiqui; M. Nazrul Islam; Muhammad Ismail; Muhammad Azhar Ehsan; Enda O'Brien; Mazen Asiri; Rayees Ahmed; et al. (Atmospheric Research, 2025)

Evaluation of antibody titer and associated risk factors of goat pox vaccine against lumpy skin disease in crossbred buffaloes - Adili Abulaiti; Zahid Naseer; Zulfiqar Ahmed; Shijun Tian; Wenju Liu; Muhammad Shoaib; Asghar Khan; Mohamed Abdelrahman; Faisal Ayub Kiani; Abid Hussain; Aftab Shaukat; Umair Riaz; et al. (Veterinary Research Communications, 2025)

Differential responses of leguminous tree species to drought stress: implications for agroforestry and restoration in arid and semi-arid climates - Muhammad Madnee; Tanveer Hussain; Muhammad Azeem Sabir; Muhammad Abid; Muneeb Khalid; Hussain Ahmad Makki; Sajjad Ali; Nugraha Akbar Nurrochmat (Agroforestry Systems, 2025)

Thriving in extremes: Adaptability potential of desert cotton Aerva javanica to hyper-arid saline conditions - Ummar Iqbal; Sana Abid; Muhammad Sharif; Sadaf Rafiq; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf (Journal of Arid Environments, 2025)

Experimental investigation of the interfacial debonding strength of class G cement and the implications to well integrity - Khizar Abid; Felipe Baena; Catalin Teodoriu; Junghun Leem; Latief Riyanto; Yon Azwa Sazali; Muhammad Syafeeq (International Journal of Greenhouse Gas Control, 2025)

Phytoremediation Capacity of Saltwort (Salsola imbricata Forssk.) Determined by Tissue Organization and Physio-biochemical traits under Arid Saline Environments - Ummar Iqbal; Muhammad Sharjeel Arif; Muhammad Sharif; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf; Sadaf Rafiq; Sana Abid (Water, Air, & Soil Pollution, 2025)

Assessing wind power generation potential over South Asia using wind speed observation and reanalysis datasets - Muhammad Abid Khan; Koji Dairaku; Saurabh Kelkar (Stochastic Environmental Research and Risk Assessment, 2025)

Organic Amendments Enhanced Phytoremediation, Physio-Chemical Functions, Growth and Productivity of Zea mays L. in Diesel-Contaminated Soil - Muhammad Sarfraz Ahmad; Ghazala; Fahd Rasul; Muhammad Ibrahim; Abid Mahmood (Journal of Soil Science and Plant Nutrition, 2025)

RETRACTED ARTICLE: Salinity effects on growth, biomass production, and genetic resources for phytoremediation potential of halophyte species in the desert - Muhammad Abid; Muhammad Rafay; Tanveer Hussain; Muhammad Azeem Sabir; Muneeb Khalid; Muhammad Madnee; Hussain Ahmed Makki; Muhammad Qasim; Ehab I. Taha; Mounir M. Bekhit; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Peptide-based vaccine design against Hendra virus through immunoinformatics approach - Asifa Sarfraz; Irfa Chaudhary; Fizza Arshad; Muhammad Shehroz; Asia Perveen; Umar Nishan; Abid Ali; Riaz Ullah; Abdelaaty A. Shahat; Aqal Zaman; Mohibullah Shah (Veterinary Immunology and Immunopathology, 2025)

In-vitro and in-vivo assessments of greenly synthesized iron oxide nanoparticles from Cascabela thevetia plant extract for the treatment of ventricular septal defect - Amina Abid; Muhammad Naveed; Tariq Aziz; Muhammad Aqib Shabbir; Hira Mubeen; Ayaz Ali Khan; Abdullah F Alsmari (South African Journal of Botany, 2025)

Photovoltaic module efficiency enhancement system by novel cooling techniques: Effect of phase change material and fins - Saad Saeed; Abid Hussain; Imran Ali; Hanzla Shahid; Muhammad Anwar; Hafiz Muhammad Ali (Process Safety and Environmental Protection, 2025)

The role of taxation in environmental sustainability in G-20 economies: A double dividend theoretical assessment - Assidi Soufiene; Rafael Alvarado; Mehdi Abid; Brayan Tillaguango; Muhammad Shahbaz (Journal of Environmental Management, 2025)

Modified approach to estimate effective porosity using density and neutron logging data in conventional and unconventional reservoirs - Muhammad Abid; Jing Ba; Uti Ikitsombika Markus; Zeeshan Tariq; Syed Haroon Ali (Journal of Applied Geophysics, 2025)

Catalytic charge synergy on Ni/Sr@rTiO2 system to promote hydrogen evolution for the implementation of green energy technologies - Ejaz Hussain; Sidra Khan; Muhammad Jalil; Muhammad Zeeshan Abid; Abdul Rauf; Nagina Naveed Riaz; Abeer Hashem; Ajay Kumar; Elsayed Fathi Abd_Allah; Khezina Rafiq (Fuel, 2025)

Corrigendum to “Uniformly dispersed flowery EuZrSe3 derived from the europium-based metal–organic framework for energy storage devices” [Fuel 336 (2023) 127066] - Abdul Ghafoor Abid; Soumaya Gouadria; Sumaira Manzoor; Khadijah Mohammed Saleh Katubi; Karam Jabbour; Muhammad Abdullah; Mehar Un Nisa; Salma Aman; Mohammed Sultan Al-Buriahi; Muhammad Naeem Ashiq (Fuel, 2025)

Bio-templating approach and DFT study of ZrMo@KIT-6 catalyst for the conversion of deep fried oil into sustainable biodiesel production - Muhammad Noman; Muhammad Farooq; Anita Ramli; Ghazala Abid; Fouzia Perveen; Dur Muhammad; Rida Ihsan; Faizan Jamil; Ali Raza Ayub; Noor Saeed khattak; Ata Ur Rahman (Fuel, 2025)

Unveiling the surface potential and selectivity of Ti3C2Tx/rGO adsorbents for arsenic removal from water system - Muhammad Zeeshan Abid; Khezina Rafiq; Aqsa Khan Buzdar; Muhammad Zaryab Waleed; Ejaz Hussain (Journal of Cleaner Production, 2025)

Probiotic potential and biotechnological characterization of the selected enterococcal strains - Abrar Hussain; Muhammad Shakeel; Muhammad Tanweer Khan; Syed Abid Ali (Food Bioscience, 2025)

Teratological abnormalities in hard ticks (Acari: Ixodidae) from Pakistan - Ejaz Akbar; Shafi Ullah; Mashal M. Almutairi; Iram Liaqat; Muhammad Adnan; Abdulaziz Alouffi; Tetsuya Tanaka; Abid Ali (Experimental and Applied Acarology, 2025)

Pollution level assessment, source apportionment, and health hazards of heavy metals and rare earth elements in the sediment core from the coast of Karachi, Pakistan - Naila Siddique; Muhammad Zaman Chaudhary; Mavia Anjum; Jawaria Abid (Marine Pollution Bulletin, 2024)

Encapsulation, optimization, and characterization of lycopene using soy protein isolate-peach gum conjugate as wall material - Arif Hussain; Muhammad Hussain; Waqas Ashraf; Khubaib Ali; Abid Hussain; Hsu Mon Phyo; Muhammad Umair Khalid; Mudassar Hussain; Zhang Lianfu (Food Bioscience, 2024)

Molecular genetics, neuroimaging outcomes, and structural analyses of novel and recurrent variants of WDR62 gene in two consanguineous Pakistani families with autosomal recessive primary microcephaly - Komal Aslam; Aysha Saeed; Hafiza Iqra Saeed; Rasheeda Bashir; Hanna Abid; Roeha Akhtar; Nida Habib; Ramisha Khan; Roha Asif; Shereen Rafiq; Maria Asif; Ehtisham Ul Haq Makhdoom; et al. (Molecular Biology Reports, 2024)

Movement of amphibians in a habitat mosaic of agriculture landscape - Waseem Ahmed; Muhammad Rais; Ayesha Akram; Muhammad Saeed; Luqman; Sumbul Gill; Aamina Abid; Abdul Hadi (European Journal of Wildlife Research, 2024)

Enhanced cadmium immobilization in soil using Fe- and Zn-doped biochar: Mechanisms and safety implications for Cicer arietinum L - Uzma Muzaffar; Muhammad Naveed; Zainab Naseem; Iqra Abid; Kashif Zulfiqar Amir; Saud Alamri; Muhammad Siddique; Martin Brtnicky; Adnan Mustafa (Chemosphere, 2024)

A cutting–edge approach to remove arsenic contents from ground water via sulfur doped copper ferrites (S–CuFe2O4) † - Ejaz Hussain; Aqsa Khan Buzdar; Muhammad Zeeshan Abid; Abdul Rauf; Khezina Rafiq (Journal of Environmental Management, 2024)

Microbial Ecosystems as Guardians of Food Security and Water Resources in the Era of Climate Change - Muhammad Danish Toor; Muneeb Ur Rehman; Javeria Abid; Dibyajyoti Nath; Izhar Ullah; Abdul Basit; Muhammad Mughees Ud Din; Heba I. Mohamed (Water, Air, & Soil Pollution, 2024)

The importance of sharing: wild plant knowledge in three valleys of Northern Pakistan - Adnan Ali Shah; Abid Raza; Naji Sulaiman; Dipak Khadka; Abdul Majid; Muhammad Abdul Aziz; Arshad Mehmood Abbasi; Mushtaq Ahmad; Andrea Pieroni (Plant Biosystems, 2024)

Toxicity of different nitrogenous fertilizers on Aedes aegypti larvae (Linnaeus) (Diptera: Culicidae) - Sikander Ali; Unsar Naeem-Ullah; Naeem Iqbal; Hafiz Azhar Ali Khan; Allah Ditta Abid; Muhammad Sohail Shahzad; Shafqat Saeed; Muhammad Usman; Muhammad Nadir Naqqash (International Journal of Tropical Insect Science, 2024)

Valorization of poultry slaughter wastes via extraction of three structural proteins (gelatin, collagen and keratin): A sustainable approach for circular economy - Muhammad Talha; Muhammad Tanveer; Aqsa Abid; Abid Aslam Maan; Muhammad Kashif Iqbal Khan; Hira Shair; Nimra Tanveer; Almas Mustafa (Trends in Food Science & Technology, 2024)

Exploring the interface dynamics of emulsion gel via a novel non-destructive technique provides insights into the underlying mechanism of gel formation, water mobility, functionality and structural variations - Abdul Qayum; Arif Rashid; Asif Ali Khan; Mingming Zhong; Yuxuan Liu; Muhammad Hussain; Muhammad Safiullah Virk; Zahoor Ahmed; Abdur Rehman; Abid Hussain; Qiufang Liang; Xiaofeng Ren; et al. (Food Bioscience, 2024)

Effect of the polyelectrolyte multilayers' charge on water splitting, fluxes of ions, selectivities and current efficiencies in ion transport through membranes - Muhammad Ahmad; Mahmood Ahmed; Abid Ali; Tanveer A. Wani; Khuram Khalid; Ijaz Ali (Desalination, 2024)

Low doses of entomopathogens matter hugely, gateway to resistance development and retarded growth in Helicoverpa armigera - Mirza Abdul Qayyum; Zhuo Zhihang; Waqas Wakil; Habib Ali; Abid Ali; Muhammad Usman Ghazanfar; Muhammad Yasin; Xu Danping; Hasham S. Almoallim; Mohammad Javed Ansari; Muhammad Tahir; Kashif Ali; et al. (Journal of Plant Diseases and Protection, 2024)

Predictability of the early summer surface air temperature over Western South Asia - Irfan Ur Rashid; Muhammad Adnan Abid; Marisol Osman; Fred Kucharski; Moetasim Ashfaq; Antje Weisheimer; Mansour Almazroui; José Abraham Torres-Alavez; Muhammad Afzaal (Climate Dynamics, 2024)
Variability of the Surface Air Temperature (SAT) over the Western South Asia (WSA) region leads to frequent heatwaves during the early summer (May-June) season. The present study uses the European Centre for Medium-Range Weather Forecast’s fifth-generation seasonal prediction system, SEAS5, from 1981 to 2022 based on April initial conditions (1-month lead) to assess the SAT predictability during early summer season. The goal is to evaluate the SEAS5’s ability to predict the El Niño-Southern Oscillation (ENSO) related interannual variability and predictability of the SAT over WSA, which is mediated through upper-level (200-hPa) geopotential height anomalies. This teleconnection leads to anomalously warm surface conditions over the region during the negative ENSO phase, as observed in the reanalysis and SEAS5. We evaluate SEAS5 prediction skill against two observations and three reanalyses datasets. The SEAS5 SAT prediction skill is higher with high spatial resolution observations and reanalysis datasets compared to the ones with low-resolution. Overall, SEAS5 shows reasonable skill in predicting SAT and its variability over the WSA region. Moreover, the predictability of SAT during La Niña is comparable to El Niño years over the WSA region.

Comprehensive chemical profiling with UHPLC-MS, in-vitro, in-silico, and in-vivo antidiabetic potential of Typha domingensis Pers; A novel source of bioactive compounds - Rizwana Dilshad; Kashif-ur-Rehman Khan; Rihana Dilshad; Saeed Ahmad; Huma Rao; Umair Khurshid; Sultan Ahmad; Maqsood Ahmad; Hafiz Muhammad Usman Abid; Muhammad Kashif Zaman; Rabia Nisar; Saharish Khaliq; et al. (South African Journal of Botany, 2024)

Quantitative and qualitative approach for accessing and predicting food safety using various web-based tools - Hafiz Muhammad Rizwan Abid; Nimrah Khan; Athar Hussain; Zainab Bintay Anis; Muhammad Nadeem; Nauman Khalid (Food Control, 2024)

Molecular identification and characterization of iris yellow spot virus (IYSV) and garlic virus X (GVX) infecting Allium species - Muhammad Usman Shahid; Abid Riaz; Tahira Shafique; Mayasar I. Al-zaban; Diaa Abd El-Moneim; Sheikh Mansoor; Yong Suk Hung; Hyeon-Jin Sun (Plant Biotechnology Reports, 2024)

Innovating for sustainability: exploring the synergy between international digital trade, appeal mechanisms, renewable energy, and economic growth on ecological footprint in BRICST economies - Muhammad Abid Hussain Shah; Wu Ximei (Environment, Development and Sustainability, 2024)

Unveiling the impact of textile materials to prevent viral infections: Urgency for awareness and public safety† - Muhammad Zaryab Waleed; Khezina Rafiq; Muhammad Zeeshan Abid; Muhammad Burhan; Raed H. Althomali; Shahid Iqbal; Ejaz Hussain (Journal of Environmental Chemical Engineering, 2024)

Florfenicol removal from veterinary pharmaceutical effluents: Tri-metallic zeolite 5A° for electrochemical oxidation and catalytic ceramic membrane separation - Amir Ikhlaq; Maryam Gull; Afnan Sajid; Khurram Saleem Joya; Muhammad Raashid; Osama Shaheen Rizvi; Zafar Masood; Salman Ahmed; Maryam Abid; Maham Hanif; Hafiz Abdul Aziz; Thamer Abdulhameed Al Johani; et al. (Journal of Environmental Chemical Engineering, 2024)

Identification of provenance of Basmati rice grown in different regions of Punjab through multivariate analysis - Muhammad Saifullah; Awais Nisar; Ramzan Akhtar; Syed M. Husnain; Shamila Imtiaz; Bashir Ahmad; Munib Ahmed Shafique; Saira Butt; Muhammad Arif; Abid Majeed Satti; Muhammad Shahzad Ahmed; Simon D. Kelly; et al. (Food Chemistry, 2024)

Emerging high intensity ultrasound for soymilk in boosting bioactivity, amino acids release, reducing anti-nutritional factors and allergenicity - Muhammad Hussain; Hao Zhong; Kifayat Hussain; Muhammad Faisal Manzoor; Abdul Qayum; Xiaofeng Liu; Jie Xu; Abid Hussain; Hafiz Muhammad Ahsan; Rongfa Guan (Food Bioscience, 2024)

Advanced strategies to mitigate heavy metals in ground and sewage water - Muhammad Mahmood Ahmed; Tuba Tariq; Mirza Abid Mehmood; Muhammad Ashfaq; Murtaza Hasan (Current Opinion in Green and Sustainable Chemistry, 2024)

Yeast-based solutions in controlling plant pathogens - Amjad Ali; Fatih Ölmez; Muhammad Ahmad Zeshan; Mustansar Mubeen; Yasir Iftikhar; Ashara Sajid; Muhammad Abid; Ajay Kumar; Praveen Kumar Divvela; Manoj Kumar Solanki (Biocatalysis and Agricultural Biotechnology, 2024)

Cu-TiO2-Aluminosilicate Nanocomposite as Highly Efficient Photocatalyst for Sustainable Removal of Cefixime Antibiotic: Synthesis, Optimization, and Toxicity Evaluation - Muhammad Umar Farooq; Qurat-Ul-Ain; Muhammad Irfan Jalees; Mahnoor Abid; Mirza Nadeem Ahmad; Maira Kaleem; Asma Tufail Shah; Juan Joon Ching (Environmental Processes, 2024)

SPEEDY-NEMO: performance and applications of a fully-coupled intermediate-complexity climate model - Paolo Ruggieri; Muhammad Adnan Abid; Javier García-Serrano; Carlo Grancini; Fred Kucharski; Salvatore Pascale; Danila Volpi (Climate Dynamics, 2024)
A fully-coupled general circulation model of intermediate complexity is documented. The study presents an overview of the model climatology and variability, with particular attention to the phenomenology of processes that are relevant for the predictability of the climate system on seasonal-to-decadal time-scales. It is shown that the model can realistically simulate the general circulation of the atmosphere and the ocean, as well as the major modes of climate variability on the examined time-scales: e.g. El Niño-Southern Oscillation, North Atlantic Oscillation, Tropical Atlantic Variability, Pacific Decadal Variability, Atlantic Multi-decadal Variability. Potential applications of the model are discussed, with emphasis on the possibility of generating sets of low-cost large-ensemble retrospective forecasts. We argue that the presented model is suitable to be employed in traditional and innovative model experiments that can play a significant role in future developments of seasonal-to-decadal climate prediction.

Melatonin alleviates cadmium phytotoxicity through regulation of growth, photosynthesis, and antioxidant potential in two pepper genotypes - Muhammad Saqib; Umbreen Shahzad; Zakia Abid; Faisal Zulfiqar; Rahul Kumar Tiwari; Milan Kumar Lal; Waleed Amjad Khan; Mohamed A. El-Sheikh; Muhammad Ahsan Altaf (Acta Physiologiae Plantarum, 2024)

Occurrence of natural enemies in maize and the predatory potential of selected arthropods against fall armyworm in Multan, Pakistan - Saleem Riaz; Muhammad Ishtiaq; Fawad Zafar Ahmad Khan; Ghulam Ali; Mirza Abid Mehmood; Muhammad Sohail Qamar Zaman (International Journal of Tropical Insect Science, 2024)

An appealing review of industrial and nutraceutical applications of pistachio waste - Syed Ali Hassan; Mueen Abbas; Sania Zia; Abid Aslam Maan; Muhammad Kashif Iqbal Khan; Abdo Hassoun; Aamir Shehzad; Richard Gattin; Rana Muhammad Aadil (Critical Reviews in Food Science and Nutrition, 2024)

Unveiling the green horizon: A bibliometric analysis of global foreign direct investment research and its emphasis on climate change - Muhammad Shabbar Raza; Yusheng Wang; Abdul Rauf; Noshaba Aziz; Muhammad Ajmal Khan; Abid Hussain (Journal of Cleaner Production, 2024)

Zinc-Coated Urea with Gelatin-Enhanced Zinc Biofortification, Apparent Nitrogen Recovery, and Ryegrass Production - Bilal Abdullah; Muhammad Bilal Khan Niazi; Zaib Jahan; Tariq Shah; Umer Shahzad Malik; Bilal Beig; Abid Mahmood; Ghulam Abbas Shah; Zahid Iqbal (Journal of Soil Science and Plant Nutrition, 2024)

Compositional shifts in rhizobacterial communities of Brassica napus under salinity stress - Muhammad Laiq; Muhammad Atif Azeem; Sara Begum; Nausheen Nazir; Zakia Ahmad; Sana Ullah; Mohammad Nisar; Abid Ullah (Applied Soil Ecology, 2024)

New trends in functionalities and extraction of plant proteins in designing plant-based meat analogues: A critical review - Aaysha Ihsan; Zia Ahmad; Jie Zheng; Muhammad Bilal; Hafiz Muhammad Rizwan Abid; Aijun Hu (Food Bioscience, 2024)

Beyond contamination: Enhancing plant tolerance to arsenic through phytobial remediation - Saeed ur Rahman; Xinxin Liu; Muhammad Khalid; Asad Rehman; Junfeng Cao; Sadaf-Ilyas Kayani; Muhammad Naeem; Naveed Ahmad; Abid Ali Khan; Muhammad Aamir Manzoor; Chang Zhao; Haoxin Tan; et al. (South African Journal of Botany, 2024)

Advancements in Ni and Co-based catalysts for sustainable syngas production via Bi-reforming of methane: A review of recent advances - Syed Muhammad Wajahat ul Hasnain; Ahmad Salam Farooqi; Bamidele Victor Ayodele; Abid Salam Farooqi; Khairuddin Sanaullah; Bawadi Abdullah (Journal of Cleaner Production, 2024)

Quantifying future water-saving potential under climate change and groundwater recharge scenarios in Lower Chenab Canal, Indus River Basin - Muhammad Shafeeque; Mohsin Hafeez; Abid Sarwar; Arfan Arshad; Tahira Khurshid; Muhammad Irfan Asim; Shoaib Ali; Adil Dilawar (Theoretical and Applied Climatology, 2024)
Quantifying water-saving potential (WSP) is crucial for sustainable water resource management in canal command areas and river basins. Previous studies have partially or fully ignored the importance of groundwater in WSP assessments, particularly in irrigated areas. This study is aimed at quantifying WSP in the Lower Chenab Canal (LCC) command area of the Indus River Basin, Pakistan, under various scenarios of future climate change and groundwater recharge. These quantifications are conducted using an empirical model based on the Budyko theory. The model was forced using observed, remote sensing, and CMIP6 future climate data for two Shared Socioeconomic Pathways (SSP245 and SSP585) and their ensembles (cold-dry, cold-wet, warm-dry, and warm-wet) for possible futures. The results showed that the average WSP in the LCC command area was 466 ± 48 mm/year during the historical period (2001–2020). The WSP is projected to decrease by – 68 ± 3% under the warm-dry ensemble scenario (SSP245 and SSP585) and – 48 ± 13% under the ensembled cold-wet scenario by 2100. The results also demonstrated that WSP could be increased by up to 70 ± 9% by artificially recharging 20% of the abstracted groundwater per year in the LCC command area by the late twenty-first century. Our findings highlight the importance of adopting artificial groundwater recharge to enhance the WSP and sustainably manage water resources in the LCC command area. Policymakers should consider these findings when deciding on water resource management in the Indus River Basin.

Surface sensitization of TiO2 via Pd/Rb2O cocatalysts: Mechanistic insights to the arsenic elimination from ground drinking water† - Kashaf Ul Sahar; Khezina Rafiq; Muhammad Zeeshan Abid; Ubaid ur Rehman; Ujala Quyyum; Abdul Rauf; Ejaz Hussain (Journal of Environmental Chemical Engineering, 2023)

Growth of tunable Au-BaO@TiO2/CdS heterostructures: Acceleration of hydrogen evolution from water splitting - Mamoona Sabir; Khezina Rafiq; Muhammad Zeeshan Abid; Ujala Quyyum; Syed Shoaib Ahmad Shah; Muhammad Faizan; Abdul Rauf; Shahid Iqbal; Ejaz Hussain (Fuel, 2023)

Rainwater harvesting for agriculture development using multi-influence factor and fuzzy overlay techniques - Xiangtian Zheng; Abid Sarwar; Fakhrul Islam; Abdul Majid; Aqil Tariq; Muhammad Ali; Shazia Gulzar; Muhammad Ismail Khan; Muhammad Akmal Sardar Ali; Muhammad Israr; Ahsan Jamil; Muhammad Aslam; et al. (Environmental Research, 2023)

Geocellular Modeling of the Cambrian to Eocene Multi-Reservoirs, Upper Indus Basin, Pakistan - Muhsan Ehsan; Muhammad Ali Umair Latif; Abid Ali; Ahmed E. Radwan; Muhammad Attique Amer; Kamal Abdelrahman (Natural Resources Research, 2023)

Heavy metals contamination in vegetables irrigated with wastewater: a case study of underdeveloping regions of Pakistan - Ana Aslam; Asifa Naz; Syed Shahid Hussain Shah; Farah Rasheed; Raheela Naz; Amina Kalsom; Nisa Mukhtar; Abid Niaz; Muhammad Aftab; Irfan Rasheed; Muhammad Arfan Ul Haq; Muhammad Arif; et al. (Environmental Geochemistry and Health, 2023)

Performance and emissions characteristics of tire pyrolysis oil in diesel engine: an experimental investigation - Haseeb Yaqoob; Hafiz Muhammad Ali; Haider Abbas; Osama Abid; Muhammad Ahmad Jamil; Talha Ahmed (Clean Technologies and Environmental Policy, 2023)

Challenges, limitations, and applications of nanofluids in solar thermal collectors—a comprehensive review - Lukman Ahmed Omeiza; Muhammad Abid; Yathavan Subramanian; Anitha Dhanasekaran; Saifullah Abu Bakar; Abul Kalam Azad (Environmental Science and Pollution Research, 2023)

Characterization for optimizing the integrated management of solid waste for energy recovery and circular economy - Fariha Jabeen; Muhammad Adrees; Muhammad Ibrahim; Muhammad Waqas; Abid Mahmood; Uzma Noreen; Afifa Aslam (Environmental Science and Pollution Research, 2023)

Exploring the economic impact of institutional entrepreneurship, social Innovation, and poverty reduction on carbon footprint in BRICS countries: what is the role of social enterprise? - Fairtown Zhou Ayoungman; Abid Hossain Shawon; Rizwan Raheem Ahmed; Muhammad Kamran Khan; Md. Shoriful Islam (Environmental Science and Pollution Research, 2023)

Risk assessment of toxic and hazardous metals in paddy agroecosystem by biochar-for bio-membrane applications - Muhammad Kashif Irshad; Sihang Zhu; Wasim Javed; Jong Cheol Lee; Abid Mahmood; Sang Soo Lee; Shang Jianying; Gadah Albasher; Atif Ali (Chemosphere, 2023)

Moisture sources for precipitation variability over the Arabian Peninsula - Matthew F. Horan; Fulden Batibeniz; Fred Kucharski; Mansour Almazroui; Muhammad Adnan Abid; Joshua S. Fu; Moetasim Ashfaq (Climate Dynamics, 2023)
We apply the Lagrangian-based moisture back trajectory method to two reanalysis datasets to determine the moisture sources for wet season precipitation over the Arabian Peninsula, defined as land on the Asian continent to the south of the Turkish border and west of Iran. To accomplish this, we make use of the evaporative source region between 65°W–120°E and 30°S–60°N, which is divided into twelve sub-regions. Our comparison of reanalyses and multiple observations allows us to validate datasets and highlight broad-scale similarities in characteristics, notwithstanding some inconsistencies in the southwest AP. The results indicate north-to-south spatiotemporal heterogeneity in the characteristics of dominant moisture sources. In the north, moisture for precipitation is mainly sourced from midlatitude land and water bodies, such as the Mediterranean and Caspian Seas. Areas further south are dependent on moisture transport from the Western Indian Ocean and parts of the African continent. The El Niño-Southern Oscillation (ENSO) exhibits an overall positive but sub-seasonally varying influence on the precipitation variability over the region, with noticeable moisture anomalies from all major source regions. A significant drying trend exists over parts of the Peninsula, which both reanalyses partially attribute to anomalies in the moisture advection from the Congo Basin and South Atlantic Ocean. However, considerable uncertainty in evaporation trends over the terrestrial evaporative sources in observations warrants additional modeling studies to further our understanding of key processes contributing to the negative trends.

Inhibition of nitrous oxide reduction in forest soil microcosms by different forms of methanobactin - Jin Chang; Peng Peng; Muhammad Farhan Ul‐Haque; Abid Hira; Alan A. DiSpirito; Jeremy D. Semrau (Environmental Microbiology, 2023)
Copper plays a critical role in controlling greenhouse gas emissions as it is a key component of the particulate methane monooxygenase and nitrous oxide reductase. Some methanotrophs excrete methanobactin (MB) that has an extremely high copper affinity. As a result, MB may limit the ability of other microbes to gather copper, thereby decreasing their activity as well as impacting microbial community composition. Here, we show using forest soil microcosms that multiple forms of MB; MB from Methylosinus trichosporium OB3b (MB‐OB3b) and MB from Methylocystis sp. strain SB2 (MB‐SB2) increased nitrous oxide (N 2 O) production as well caused significant shifts in microbial community composition. Such effects, however, were mediated by the amount of copper in the soils, with low‐copper soil microcosms showing the strongest response to MB. Furthermore, MB‐SB2 had a stronger effect, likely due to its higher affinity for copper. The presence of either form of MB also inhibited nitrite reduction and generally increased the presence of genes encoding for the iron‐containing nitrite reductase ( nirS ) over the copper‐dependent nitrite reductase ( nirK ). These data indicate the methanotrophic‐mediated production of MB can significantly impact multiple steps of denitrification, as well as have broad effects on microbial community composition of forest soils.

Utilization of cereal-based husks to achieve sustainable development goals: Treatment of wastewater, biofuels, and biodegradable packaging - Syed Ali Hassan; Mueen Abbas; Waqar Mujahid; Waqar Ahmed; Saeed Ahmad; Abid Aslam Maan; Aamir Shehzad; Zuhaib F. Bhat; Rana Muhammad Aadil (Trends in Food Science & Technology, 2023)

Exogenous foliar application of melatonin mitigates salt induced oxidative stress and promotes growth in Gerbera jamosonii - Faisal Zulfiqar; Anam Moosa; Antonio Ferrante; Muhammad Nafees; Anastasios Darras; Muhammad Mudassir Nazir; Islem Abid; Tarek M.A. Soliman (South African Journal of Botany, 2023)

Effects of citrus pomace on mechanical, sensory, phenolic, antioxidant, and gastrointestinal index properties of corn extrudates - Muhammad Asif; Muhammad Kashif Iqbal Khan; Muhammad Issa Khan; Abid Aslam Maan; Harrison Helmick; Jozef L. Kokini (Food Bioscience, 2023)

Assessment of radiological indices and physiochemical characterization of sediments in Chashma Lake, Pakistan - Mustafa Khan; Muhammad Zaman Chaudhary; Ehsan Ullah Khan; Jawaria Abid; Tabassum Nasir; Nadeem Yaqoob (Environmental Monitoring and Assessment, 2023)

Analyzing the non-linear association between urbanization and ecological footprint: an empirical analysis - Muhammad Arif; Abid Rashid Gill; Minhaj Ali (Environmental Science and Pollution Research, 2023)

Rapid detection of ESKAPE and enteric bacteria using tapered dielectrophoresis and their presence in urban water cycle - Wan Hanna Melini Wan Mohtar; Muhammad Amirul Mohd Razali; Muhammad Abid Mazlan; Arash Zulkarnain Ahmad Rozaini; Silambarasi A.P. Mooralitharan; Aidil Abdul Hamid; Muhamad Ramdzan Buyong (Process Safety and Environmental Protection, 2023)

Piriformospora indica alter root-associated microbiome structure to enhance Artemisia annua L. tolerance to arsenic - Saeed ur Rahman; Muhammad Khalid; Nan Hui; Asad Rehman; Sadaf-Ilyas Kayani; Xueqing Fu; Han Zheng; Jin Shao; Abid Ali Khan; Mehran Ali; Ayat Taheri; Hang Liu; et al. (Journal of Hazardous Materials, 2023)

Functional characterization of DcMYB11, an R2R3 MYB associated with the purple pigmentation of carrot petiole - Vincenzo D’Amelia; Julien Curaba; Muhammad Ali Abid; Salvatore Esposito; Pablo Cavagnaro; Domenico Carputo; Massimo Iorizzo (Planta, 2023)

Hollow Mesoporous Silica Nanoparticles for Dual Chemo-starvation Therapy of Hepatocellular Carcinoma - Aftab Ullah; Marina Khan; Zhang Yibang; Faisal Raza; Muhammad Hasnat; Jin Cao; Xueyong Qi; Abid Hussain; Daojun Liu (Pharmaceutical Research, 2023)

The dynamic association between public environmental demands, government environmental governance, and green technology innovation in China: evidence from panel VAR model - Na Zhang; Jinqian Deng; Fayyaz Ahmad; Muhammad Umar Draz; Nabila Abid (Environment, Development and Sustainability, 2023)

Exploring the Intertwined Nexus between Globalization, Energy Usage, Economic Complexity, and Environmental Quality in Emerging Asian Economies: A Pathway Towards a Greener Future - Muhmmad Asim Rafiq; Abdul Rauf; Saifullah Shakir; Ameer Muhammad Aamir Abbas; Huaping Sun; Saira Abid (Environmental Science and Pollution Research, 2023)

Hydrogen, carbon dioxide, and methane adsorption potential on Jordanian organic-rich source rocks: Implications for underground H2 storage and retrieval - Amer Alanazi; Hussein Rasool Abid; Muhammad Usman; Muhammad Ali; Alireza Keshavarz; Volker Vahrenkamp; Stefan Iglauer; Hussein Hoteit (Fuel, 2023)

Microwaves as sustainable approach for artificial ripening of date fruit cv. Khupra to reduce fruit waste - Tayyaba Alvi; Muhammad Kashif Iqbal Khan; Abid Aslam Maan; Muhammad Shahid; Shyam Sablani (Food Bioscience, 2023)

Chemical composition and antimicrobial activity of Boswellia serrata oleo-gum-resin essential oil extracted by superheated steam - Muhammad Adnan Ayub; Muhammad Asif Hanif; Joanne Blanchfield; Muhammad Zubair; Muhammad Amin Abid; Muhammad Tahir Saleh (Natural Product Research, 2023)

Sustainable utilization of apple pomace and its emerging potential for development of functional foods - Muhammad Asif; Tahreem Javaid; Zafar Ullah Razzaq; Muhmmad Kashif Iqbal Khan; Abid Aslam Maan; Saria Yousaf; Ayesha Usman; Sidra Shahid (Environmental Science and Pollution Research, 2023)

Dyeing of wool fabric with natural dye extracted from Dalbergia Sissoo using natural mordants - Kashif Iqbal; Haseeb Afzal; Muhammad Owais Raza Siddiqui; Uzma Bashir; Khayale Jan; Amir Abbas; Hafiz Affan Abid (Sustainable Chemistry and Pharmacy, 2023)

The effects of short term blue light treatment on promoting nutrition value in Chinese cabbage - Ruixing Zhang; Yulin Liu; Qiming Pan; Abid Khan; Xue Bai; Muhammad Ali; Wenjing Yang; Lugang Zhang; Baohua Li (Food Chemistry, 2023)

Exploration of plant growth promoting traits and regulatory mechanisms of Bacillus anthracis PM21 in enhancing salt stress tolerance in maize - Muhammad Atif Azeem; Fawad Ali; Abid Ullah; Mahmood Iqbal; Kishwar Ali; Dunia A. Al Farraj; Mohamed S. Elshikh; Qirat Naz; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2023)

Biocompatible cellulose acetate supported ammonium based ionic liquid membranes; way forward to remediate water pollution - Amina Khalid; Sana Zulfiqar; Noshabah Tabassum; Amir Sada Khan; Muhammad Amin Abid; Muhammad Saeed Akhtar; Fahad Al-Misned; Ahmed Muteb Aljuwayid; Sasan Zahmatkesh; Saira Asif (Chemosphere, 2023)

Erratum to ‘Role of endophytic bacteria in salinity stress amelioration by physiological and molecular mechanisms of defense: A comprehensive review’ South African Journal of Botany, Volume 151, December 2022, Pages 33-46 - Baber Ali; Aqsa Hafeez; Muhammad Ammar Javed; Muhammad Siddique Afridi; Hina Ali Abbasi; Ayesha Qayyum; Tayyaba Batool; Abid Ullah; Romina Alina Marc; Soad K. Al Jaouni; Dalal Hussien M. Alkhalifah; Samy Selim (South African Journal of Botany, 2023)

Uniformly dispersed flowery EuZrSe3 derived from the europium-based metal–organic framework for energy storage devices - Abdul Ghafoor Abid; Soumaya Gouadria; Sumaira Manzoor; Khadijah Mohammed Saleh Katubi; Karam Jabbour; Muhammad Abdullah; Mehar Un Nisa; Salma Aman; Mohammed Sultan Al-Buriahi; Muhammad Naeem Ashiq (Fuel, 2023)

Development of CuO/CuS/MnO2 ternary nanocomposite for visible light-induced photocatalytic degradation of methylene blue - Muhammad Abdullah; Peter John; Muhammad Naeem Ashiq; Sumaira Manzoor; Muhammad Ishfaq Ghori; Mehar Un Nisa; Abdul Ghafoor Abid; Kashif Younas Butt; Saeed Ahmed (Nanotechnology for Environmental Engineering, 2023)

An assessment of the efficacy of biochar and zero-valent iron nanoparticles in reducing lead toxicity in wheat (Triticum aestivum L.). - Muhammad Nauman Mahamood; Sihang Zhu; Ali Noman; Abid Mahmood; Sana Ashraf; Muhammad Aqeel; Muhammad Ibrahim; Sobia Ashraf; Rock Keey Liew; Su Shiung Lam; Muhammad Kashif Irshad (Environmental Pollution, 2023)

A review of particulate pollution over Himalaya region: Characteristics and salient factors contributing ambient PM pollution - Muhammad Azher Hassan; Tariq Mehmood; Junjie Liu; Xiaosan Luo; Xinghua Li; Mohsin Tanveer; Muhammad Faheem; Awais Shakoor; Afzal Ahmed Dar; Muhammad Abid (Atmospheric Environment, 2023)

Towards developing resistance to chickpea chlorotic dwarf virus through CRISPR/Cas9-mediated gene editing using multiplexed gRNAs - Muniba Abid Munir Malik; Muhammad Saleem Haider; Ying Zhai; Muhammad Azmat Ullah Khan; Hanu R. Pappu (Journal of Plant Diseases and Protection, 2023)

Two are better than one: the combinations of Beauveria bassiana, diatomaceous earth, and indoxacarb as effective wheat protectants - Waqas Wakil; Nickolas G. Kavallieratos; Erifili P. Nika; Abid Ali; Taha Yaseen; Muhammad Asrar (Environmental Science and Pollution Research, 2023)
The current study evaluates the efficacy of the entomopathogenic fungus Beauveria bassiana (Balsamo-Crivelli) Vuillemin (Hypocreales: Cordycipitaceae), diatomaceous earth (DE) (Protect-It), and the oxadiazine indoxacarb, at single or combined applications on wheat kernels, for the management of the rusty grain beetle, Cryptolestes ferrugineus (Stephens) (Coleoptera: Laemophloeidae), the red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae), the khapra beetle, Trogoderma granarium Everts (Coleoptera: Dermestidae), and the lesser grain borer, Rhyzopertha dominica (F.) (Coleoptera: Bostrychidae). The study was conducted between November 2020 and August 2021 in Faisalabad under a complete randomized block design. The combination of DE + indoxacarb was the most efficient as it caused higher overall mortalities ranging between 59.34 and 100%, and lower overall progeny production ranging between 8.35 and 33.70 individuals per vial, than all other treatments. Beauveria bassiana alone exhibited the lowest mortality rates ranging between 22.33 and 47.76%, and the highest offspring emergence, ranging between 51.33 and 78.55 individuals per vial. Similar pattern was observed when persistence bioassays were conducted. For a period of 120 days, the DE + indoxacarb was the most powerful combination against all tested species, providing overall mortality rates between 17.06 and 63.80%. The overall progeny production was lower for the insect individuals exposed on wheat treated with the DE + indoxacarb combination, ranging between 13.66 and 52.23 individuals per vial, and higher for those exposed to B. bassiana alone, ranging between 44.03 and 107.67 individuals per vial, for the entire duration of storage. However, the efficacy of all treatments decreased gradually during the course of storage. The findings of the current study indicate that the combinations of entomopathogenic fungi, DE, and indoxacarb can be used for the prolonged protection of stored wheat from the tested noxious insect species of stored products. Further research, which will include other inert dusts in combination with entomopathogenic fungi and indoxacarb, may provide additional knowledge towards an effective management of noxious species occurring in storages.

Pollen morphology of Lactuca L. (s. lat.) (Cichorieae: Asteraceae) from Hindukush, Western Himalayan and Karakorum ranges and its taxonomic significance - Roohi Abid; Muhammad Qaiser (Palynology, 2023)

DNNGP, a deep neural network-based method for genomic prediction using multi-omics data in plants - Kelin Wang; Muhammad Ali Abid; Awais Rasheed; Jose Crossa; Sarah Hearne; Huihui Li (Molecular Plant, 2023)

Polyelectrolyte multilayers coating of aliphatic polyamide anion-exchange membranes to increase monovalent/divalent anions selectivity in electrodialysis - Muhammad Ahmad; Mahmood Ahmed; Shabbir Hussain; Abid Ali; Manzar Zahra; Muhammad Imran Din; Zeeshan Mustafa (Desalination, 2023)

A quantitative assessment of pollution from potentially toxic elements in groundwater and the accompanying health risks - Atif Muhmood; Abdul Majeed; Abid Niaz; Asrar Hussain Shah; Ali Afzal; Khaliq ur Rehman Arshad; Muhammad Rashid; Arslan Nazarat (Arabian Journal of Geosciences, 2022)

Mechanisms of β-adrenergic receptors agonists in mediating pro and anti-apoptotic pathways in hyperglycemic Müller cells - Sher Zaman Safi; Laiba Saeed; Humaira Shah; Zahina Latif; Abid Ali; Muhammad Imran; Nawshad Muhammad; Talha Bin Emran; Vetriselvan Subramaniyan; Ikram Shah Bin Ismail (Molecular Biology Reports, 2022)

Assessing Salt Tolerance Induction in Potato by Salicylic Acid Using Morpho-Physio-Biochemical, Ionic, and Yield Indices - Hafiz Nazar Faried; C. M. Ayyub; Fahad Masoud Wattoo; Mohsin Bashir; Kashif Razzaq; Gulzar Akhtar; Abid Hussain; Sami Ullah; Javed Iqbal Wattoo; Muhammad Amin; Shoaib Munir; Muhammad Rashid Shaheen; et al. (Potato Research, 2022)

Early summer surface air temperature variability over Pakistan and the role of El Niño–Southern Oscillation teleconnections - Irfan Ur Rashid; Muhammad Adnan Abid; Mansour Almazroui; Fred Kucharski; Muhammad Hanif; Shaukat Ali; Muhammad Ismail (International Journal of Climatology, 2022)
Early summer (May–June) is the season where the surface air temperature (SAT) variability is largest and may result in extreme temperature conditions over Pakistan. Therefore, we analysed the early summer interannual SAT variability over Pakistan for the period 1981–2018 using observational dataset and model simulations. We noted that upper‐level anticyclonic circulation anomalies over Pakistan, which are associated with upper to the middle tropospheric descending motion, favour clear skies with an increase in net shortwave radiation that leads to extreme surface warming over the region. Moreover, the El Niño–Southern Oscillation (ENSO) based on Niño3.4 SST index is negatively associated with SAT anomalies over Pakistan. The cold ENSO phase favours the positive geopotential height anomalies due to the strengthening of the Walker circulation that enhance the sinking motion and result in less cloudiness leading to the extreme higher surface temperature conditions over Pakistan, while the opposite happens in the warm ENSO phase. Moreover, the Saudi‐KAU Atmospheric Global Climate Model (AGCM) simulated large‐scale patterns that are in good agreement with the observations. Sensitivity experiments with the AGCM confirm that cold SST anomalies in the ENSO region significantly favour above‐normal SAT anomalies over Pakistan, while the opposite happens in the warm ENSO phase. These results are important to understand and potentially predict regional heatwaves over the South Asian region, particularly over Pakistan.

Antidiarrheal and antispasmodic activities of Trillium govanianum rhizomes extract: involvement of calcium channel blockade - Naveed Muhammad; Shafiq Ur Rahman; Hilal Uddin; Omer Shehzad; Muhammad Ismail; Niaz Ali; Aslam Khan; Muhammad Shahid; Abid Ullah; Shujaat Ahmad; Haya Hussain; Ikram ul Haq; et al. (Natural Product Research, 2022)

Characterization of functional genes GS3 and GW2 and their effect on the grain size of various landraces of rice (Oryza sativa) - Haroon Rasheed; Sajid Fiaz; Muhammad Abid Khan; Sultan Mehmood; Faizan Ullah; Sumbul Saeed; Shahid Ullah Khan; Tabassam Yaseen; Reem M. Hussain; Abdul Qayyum (Molecular Biology Reports, 2022)

Assessment of cobalt in wheat grains as affected by diverse fertilizers: implications for public health - Abid Ejaz; Kafeel Ahmad; Zafar Iqbal Khan; Shahzad Akhtar; Razia Sultana; Muhammad Nadeem; Muhammad Iftikhar Hussain; Mohamed S. Elshikh (Environmental Science and Pollution Research, 2022)

Appraising growth, daily intake, health risk index, and pollution load of Zn in wheat (Triticum aestivum L.) grown in soil differentially spiked with zinc - Abid Ejaz; Zafar Iqbal Khan; Kafeel Ahmad; Fatima Ghulam Muhammad; Shahzad Akhtar; Muhammad Iftikhar Hussain (Environmental Science and Pollution Research, 2022)

Recent approaches on the optimization of biomass gasification process parameters for product H2 and syngas ratio: a review - Muhammad Zain Siddiqui; Mahshab Sheraz; Umair Ali Toor; Ali Anus; Abid Mahmood; Muhammad Haseeb; Muhammad Ibrahim; Kuan Shiong Khoo; Vishno Vardhan Devadas; Muhammad Mubashir; Sami Ullah; Pau Loke Show (Environment, Development and Sustainability, 2022)

Green growth and sustainable development: dynamic linkage between technological innovation, ISO 14001, and environmental challenges - Nabila Abid; Federica Ceci; Muhammad Ikram (Environmental Science and Pollution Research, 2022)

Evaluation of nickel toxicity in wheat as function of diverse type of fertilizers: implications for public health - Abid Ejaz; Kafeel Ahmad; Zafar Iqbal Khan; Razia Sultana; Shahzad Akhtar; Muhammad Nadeem (Environmental Science and Pollution Research, 2022)

Hydrological evaluation of 14 satellite-based, gauge-based and reanalysis precipitation products in a data-scarce mountainous catchment - Naeem Saddique; Muhammad Muzammil; Istakhar Jahangir; Abid Sarwar; Ehtesham Ahmed; Rana Ammar Aslam; Christian Bernhofer (Hydrological Sciences Journal, 2022)

Effect of darkness treatment on the morphology, hormone status and gene expression of developing adventitious root in apple rootstock - Ke Li; Huiyue Tian; Jiangping Mao; Abid Khan; Muhammad Mobeen Tahir; Shaohuan Li; Shiyue Chen; Yun Shao; Dong Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Design, synthesis, in vitro evaluation, and docking studies on ibuprofen derived 1,3,4-oxadiazole derivatives as dual α-glucosidase and urease inhibitors - Saima Daud; Obaid-ur-Rahman Abid; Asma Sardar; Basit Ali Shah; Muhammad Rafiq; Abdul Wadood; Mehreen Ghufran; Wajid Rehman; Zain-ul-Wahab; Fatima Iftikhar; Rifhat Sultana; Habiba Daud; et al. (Medicinal Chemistry Research, 2022)

Review of hospital plastic waste management strategies for Pakistan - Yasir Qayyum Gill; Mudasar Khurshid; Umer Abid; Muhammad Wajid Ijaz (Environmental Science and Pollution Research, 2022)

A study on the contamination assessment, health risk and mobility of two heavy metals in the soil-plants-ruminants system of a typical agricultural region in the semi arid environment - Xiaoping Ge; Zafar Iqbal Khan; Fu Chen; Mubeen Akhtar; Kafeel Ahmad; Abid Ejaz; Muhammad Arslan Ashraf; Muhammad Nadeem; Shahzad Akhtar; Jawaher Alkahtani; Yheni Dwiningsih; Mohamed S. Elshikh (Environmental Science and Pollution Research, 2022)

Spatio-temporal variability of drought characteristics across Pakistan - Jae Eun Lee; Muhammad Azam; Saif Ur Rehman; Muhammad Waseem; M. Naveed Anjum; Arslan Afzal; M. J. M. Cheema; Muhammad Mehtab; Muhammad Latif; Rehan Ahmed; Muhammad Umar; Abid Sarwar; et al. (Paddy and Water Environment, 2022)

Comparative efficacy of different biochars and traditional manures in the attenuation of cadmium toxicity in rice (Oryza sativa L.) - Abdul Majeed; Atif Muhmood; Abid Niaz; Allah Ditta; Muhammad Nawaz Rajpar (Arabian Journal of Geosciences, 2022)

Farm-level autonomous adaptation to climate change and its impact on crop productivity: evidence from Pakistan - Nasir Abbas Khan; Zaiwu Gong; Ashfaq Ahmad Shah; Muhammad Abid; Uttam Khanal (Environment, Development and Sustainability, 2021)

Constituents and antibacterial activity of leaf essential oil of Plectranthus scutellarioides - Pakeeza Aziz; Nadeem Muhammad; Azeem Intisar; Muhammad Amin Abid; Muhammad Imran Din; Muhammad Yaseen; Rehana Kousar; Aqsa Aamir; Quratulain; Rabia Ejaz (Plant Biosystems, 2021)

Comparative analysis of chicken cecal microbial diversity and taxonomic composition in response to dietary variation using 16S rRNA amplicon sequencing - Zubia Rashid; Muhammad Zubair Yousaf; Syed Muddassar Hussain Gilani; Sitwat Zehra; Ashaq Ali; Abid Azhar; Saddia Galani (Molecular Biology Reports, 2021)

Occurrence, distribution, and pollution indices of potentially toxic elements within the bed sediments of the riverine system in Pakistan - Javed Nawab; Zia Ud Din; Riaz Ahmad; Sardar Khan; Mazhar Iqbal Zafar; Shah Faisal; Waleed Raziq; Hamza Khan; Zia Ur Rahman; Abid Ali; Muhammad Qayash Khan; Sajid Ullah; et al. (Environmental Science and Pollution Research, 2021)

Sources, chemistry, bioremediation and social aspects of arsenic-contaminated waters: a review - Syed Ejaz Hussain Mehdi; Rabia Amen; Awais Ali; Hirra Anjum; Abid Mahmood; Muhammad Mubashir; Ahmad Mukhtar; Sami Ullah; Abdullah G. Al-Sehemi; Muhammad Ibrahim; Mohd Shariq Khan; Muhammad Abdul Qyyum; et al. (Environmental Chemistry Letters, 2021)

Status and determinants of other gainful activities by farmers in mountainous rural regions of Gilgit-Baltistan, Pakistan - Muhammad Abid Shahzad; Vaqar Ahmed; Christian Fischer (Journal of Mountain Science, 2021)
Non-farm income sources are important for livelihood sustenance, especially in the mountainous regions of developing countries. To implement effective policies to improve economic development, policymakers need insights at the grassroots level. Yet, there is a lack of empirical evidence in the context of Pakistan. This study examines the current situation and the factors influencing the decision by farmers to engage in other gainful activities (OGAs) such as farm diversification and off-farm work in the northern mountainous regions of Pakistan. The study is based on quantitative survey data obtained from 459 farm managers and qualitative data from 24 key informants from five different districts in Gilgit-Baltistan. Utilizing a logistic regression model, a statistical analysis is conducted on farmer and farm characteristics to investigate the probability of farm managers to engage in OGAs. The survey results show that around 71% of farm managers are engaged in OGAs (with 24% in farm diversification, 61% in offfarm work and 15% in both). The share of female farm managers is 51% in farm diversification while male farm managers dominate off-farm activities (69%). The most prevalent types of farm diversification are the processing of farm products and tourism-related farm work, while the main off-farm activities are setting up grocery stores outside the farm, having salaried jobs or engaging in other non-agricultural business. There are significant differences between farmers with and without OGAs particularly regarding farmer characteristics, agricultural income and some other variables. The logit model results show that farmer characteristics mainly determine off-farm work activities while farm (and other) characteristics mostly explain farm diversification. These findings suggest that OGAs primarily exist as livelihood strategies. Farm diversification is linked with the long-term sustenance of agricultural activities while off-farm work is predominantly driven by economic needs. Both types of OGAs require specific support policies while attention needs to be given not to threaten regional food supply.

Molecular detection and prevalence of Theileria ovis and Anaplasma marginale in sheep blood samples collected from Layyah district in Punjab, Pakistan - Kainat Abid; Sundas Bukhari; Muhammad Asif; Ayesha Sattar; Maryam Arshad; Munir Aktas; Sezayi Ozubek; Rehan Sadiq Shaikh; Furhan Iqbal (Tropical Animal Health and Production, 2021)

Revisiting the relationship between carbon emission, renewable energy consumption, forestry, and agricultural financial development for China - Mansoor Ahmed Koondhar; Muhammad Shahbaz; Ilhan Ozturk; Abid Ali Randhawa; Rong Kong (Environmental Science and Pollution Research, 2021)

Impact of green trust and green perceived quality on green purchase intentions: a moderation study - Allah Wasaya; Muhammad Abid Saleem; Jamil Ahmad; Muhammad Nazam; M. Mohsin Ali Khan; Mohammad Ishfaq (Environment, Development and Sustainability, 2021)

Carrageenan oligomers and salicylic acid act in tandem to escalate artemisinin production by suppressing arsenic uptake and oxidative stress in Artemisia annua (sweet wormwood) cultivated in high arsenic soil - Muhammad Naeem; Tariq Aftab; Abid Ali Ansari; Mohammad Masroor Akhtar Khan (Environmental Science and Pollution Research, 2021)

Evaluation of transfer of lead in soil plant animal system: assessment of consequences of its toxicity - Fu Chen; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Tasneem Ahmad; Ifra Saleem Malik; Asma Ashfaq; Mudasra Munir; Sonaina Nazar; Zunaira Munir; Abid Ejaz; Muhammad Nadeem; et al. (Environmental Science and Pollution Research, 2021)

Drought Tolerance Strategies in Plants: A Mechanistic Approach - Muhammad Ilyas; Mohammad Nisar; Nadeem Khan; Ali Hazrat; Aamir Hamid Khan; Kashif Hayat; Shah Fahad; Aziz Khan; Abid Ullah (Journal of Plant Growth Regulation, 2021)

An integrated approach to evaluate the unconventional hydrocarbon generation potential of the Lower Goru Formation (Cretaceous) in Southern Lower Indus basin, Pakistan - Muhsan Ehsan; Hanming Gu; Abid Ali; Malik Muhammad Akhtar; Saiq Shakeel Abbasi; Muhammad Armaghan Faisal Miraj; Munawar Shah (Journal of Earth System Science, 2021)

Synthesis, β-glucuronidase inhibition and molecular docking studies of cyano-substituted bisindole hydrazone hybrids - Obaidurahman Abid; Syahrul Imran; Muhammad Taha; Nor Hadiani Ismail; Waqas Jamil; Syed Muhammad Kashif; Khalid Mohammed Khan; Juliana Yusoff (Molecular Diversity, 2021)

Assessment of heavy metal pollution in Brassica plants and their impact on animal health in Punjab, Pakistan - Zafar Iqbal; Farhat Abbas; Muhammad Ibrahim; Tahir Imran Qureshi; Matin Gul; Abid Mahmood (Environmental Science and Pollution Research, 2021)

Scalp Hair Metal Analysis Concerning DNA Damage in Welders of Peshawar Khyber Pakhtunkhwa Pakistan - Muhammad Khisroon; Ajmal Khan; Ashraf Ali Shah; Ihsan Ullah; Javeed Farooqi; Abid Ullah (Biological Trace Element Research, 2021)

Optimization, in vitro release and toxicity evaluation of novel pH sensitive itaconic acid-g-poly(acrylamide)/sterculia gum semi-interpenetrating networks - Fauzia Rehman; Ikram Ullah Khan; Syed Haroon Khalid; Sajid Asghar; Muhammad Irfan; Ikrima Khalid; Akhtar Rasul; Huma Mahmood; Abid Mehmood Yousaf; Yasser Shahzad; Muhammad Mudassar; Noor Ul Amin Mohsin (DARU Journal of Pharmaceutical Sciences, 2021)

Biallelic loss-of-function variants in NEMF cause central nervous system impairment and axonal polyneuropathy - Ashfaque Ahmed; Meng Wang; Gaber Bergant; Reza Maroofian; Rongjuan Zhao; Majid Alfadhel; Marwan Nashabat; Muhammad Talal AlRifai; Wafaa Eyaid; Abdulrahman Alswaid; Christian Beetz; Yan Qin; et al. (Human Genetics, 2021)

Heat stress in cultivated plants: nature, impact, mechanisms, and mitigation strategies—a review - Muhammad Umair Hassan; Muhammad Umer Chattha; Imran Khan; Muhammad Bilal Chattha; Lorenzo Barbanti; Muhammad Aamer; Muhammad Mehmood Iqbal; Muhammad Nawaz; Athar Mahmood; Abid Ali; Muhammad Talha Aslam (Plant Biosystems, 2021)

Effects of soil application of two different fipronil formulations on some soil-dwelling non-target arthropods - Muhammad Asad; Sohail Ahmed; Rashad Rasool Khan; Abid Ali; Muhammad Fahad Raza; Ammarah Shabbir; Faisal Munir; Anam Noreen Abbas; Mubashir Tariq (International Journal of Tropical Insect Science, 2021)

Influence of silicon and chitosan on growth and physiological attributes of maize in a saline field - Hafiza Samra Younas; Muhammad Abid; Muhammad Shaaban; Muhammad Ashraf (Physiology and Molecular Biology of Plants, 2021)

Synthesis, urease inhibition screening and molecular docking studies of piperonal based imine derivatives - Obaid-ur-Rahman Abid; Saima Daud; Asma Sardar; Wajid Rehman; Abdul Wadood; Ashfaq Ur Rehman; Toheed Akhter; Iram Bibi; Zaheer Ahmad; Muhammad Yasir (Medicinal Chemistry Research, 2021)

Mapping farmers’ vulnerability to climate change and its induced hazards: evidence from the rice-growing zones of Punjab, Pakistan - Nasir Abbas Khan; Qijie Gao; Muhammad Abid; Ashfaq Ahmad Shah (Environmental Science and Pollution Research, 2021)

Intraperitoneal injections of copper ferrite nanoparticles disturb blood, plasma, and antioxidant parameters of Wistar rats in a sex-specific manner - Hasna Riaz; Rimsha Hashmi; Shairyar Abid; Nisha Shareef; Abida Faqir; Aqsa Amir; Muhammad Saqib Shahzad; Muhammad Shakeel; Saeed Akhtar; Muhammad Naeem Ashiq; Ather Ibrahim; Furhan Iqbal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Molecular and morphological discrimination of Chrysanthemum indicum using allele-specific PCR and T-shaped trichome - Suleman Abid; Lalitha Kaliraj; Muhammad Huzaifa Arif; Joon Hurh; Jong Chan Ahn; Deok Chun Yang; Seok-Kyu Jung (Molecular Biology Reports, 2020)

Green remediation of saline–sodic Pb-factored soil by growing salt-tolerant rice cultivar along with soil applied inorganic amendments - Muhammad Mazhar Iqbal; Tayyaba Naz; Mazhar Iqbal Zafar; Muhammad Imtiaz; Omer Farooq; Atique ur Rehman; Shafaqat Ali; Muhammad Rizwan; Sabir Hussain; Wasim Javed; Ghulam Murtaza; Muhammad Afzal; et al. (Paddy and Water Environment, 2020)

Human health risk assessment of heavy metals in raw milk of buffalo feeding at wastewater-irrigated agricultural farms in Pakistan - Zafar Iqbal; Farhat Abbas; Muhammad Ibrahim; Tahir Imran Qureshi; Matin Gul; Abid Mahmood (Environmental Science and Pollution Research, 2020)

Modeling food growers’ perceptions and behavior towards environmental changes and its induced risks: evidence from Pakistan - Nasir Abbas Khan; Qijie Gao; Muhammad Amjed Iqbal; Muhammad Abid (Environmental Science and Pollution Research, 2020)

Evaluation of host–pathogen interactions for selection of entomopathogenic fungal isolates against Oligonychus afrasiaticus (McGregor) - Abid Hussain; Muhammad Rizwan-ul-Haq; Ahmed Mohammed AlJabr; Hassan Al-Ayedh (BioControl, 2020)

Characterization of a novel cotton MYB gene, GhMYB108-like responsive to abiotic stresses - Abid Ullah; Muhammad Tahir Ul Qamar; Mohammad Nisar; Ali Hazrat; Gul Rahim; Aamir Hamid Khan; Kashif Hayat; Saeed Ahmed; Waqar Ali; Aziz khan; Xiyan Yang (Molecular Biology Reports, 2020)

Characterization of phenolic compounds in two novel lines of Pisum sativum L. along with their in vitro antioxidant potential - Nausheen Nazir; Mohammad Nisar; Sajjad Ahmad; Syed Fazal Wadood; Tour Jan; Muhammad Zahoor; Manzoor Ahmad; Abid Ullah (Environmental Science and Pollution Research, 2020)

Isolation and genetic characterization of virulent strains of avian paramyxovirus-1 from multiple avian species in Azad Jammu and Kashmir 2017–2018 - Abid Hussain; Abdul Wajid; Safa Ather; Kashaf Alyas; Muhammad Awais; Muhammad Rizwan Khan; Tanveer Hussain; Masroor Ellahi Babar (Brazilian Journal of Microbiology, 2020)

Leea macrophylla (Roxb.) root extract reverses CCl4 induced liver injury through upregulation of antioxidative gene expression: a molecular interaction for therapeutic inception - Md. Rakibul Hassan Bulbul; Md. Atiar Rahman; Md. Zillur Rahman; Talha Bin Emran; Mirola Afroze; Mala Khan; Muhammad Abid Hasan Chowdhury; Mohammed Auwal Ibrahim; Mohammed Sohel Chowdhury (Advances in Traditional Medicine, 2020)

Copper-induced oxidative stress, initiation of antioxidants and phytoremediation potential of flax (Linum usitatissimum L.) seedlings grown under the mixing of two different soils of China - Muhammad Hamzah Saleem; Shah Fahad; Shahid Ullah Khan; Mairaj Din; Abid Ullah; Ayman EL Sabagh; Akbar Hossain; Analía Llanes; Lijun Liu (Environmental Science and Pollution Research, 2020)

Natural and semisynthetic polymers blended orodispersible films of citalopram - Yasser Shahzad; Maimoona Maqbool; Talib Hussain; Abid Mehmood Yousaf; Ikram Ullah Khan; Tariq Mahmood; Muhammad Jamshaid (Natural Product Research, 2020)

Antibiotics in poultry manure and their associated health issues: a systematic review - Juma Muhammad; Sardar Khan; Jian Qiang Su; Abd El-Latif Hesham; Allah Ditta; Javed Nawab; Abid Ali (Journal of Soils and Sediments, 2020)

Glycinebetaine alleviates the chromium toxicity in Brassica oleracea L. by suppressing oxidative stress and modulating the plant morphology and photosynthetic attributes - Rehan Ahmad; Shafaqat Ali; Muhammad Abid; Muhammad Rizwan; Basharat Ali; Asif Tanveer; Irfan Ahmad; Muhammad Azam; Muhammad Awais Ghani (Environmental Science and Pollution Research, 2020)

Effective plant-endophyte interplay can improve the cadmium hyperaccumulation in Brachiaria mutica - Muhammad Tayyab Ahsan; Razia Tahseen; Abida Ashraf; Abid Mahmood; Muhammad Najam-ul-haq; Muhammad Arslan; Muhammad Afzal (World Journal of Microbiology and Biotechnology, 2019)

Knockdown of CaHSP60-6 confers enhanced sensitivity to heat stress in pepper (Capsicum annuum L.) - Saeed ul Haq; Abid Khan; Muhammad Ali; Wen-Xian Gai; Huai-Xia Zhang; Qing-Hui Yu; Sheng-Bao Yang; Ai-Min Wei; Zhen-Hui Gong (Planta, 2019)

Estimation of secondary metabolites of indigenous medicinal plant extracts and their in vitro and in vivo efficacy against tomato early blight disease in Pakistan - Sobia Chohan; Rashida Perveen; Muhammad Anees; Muhammad Azeem; Muhammad Abid (Journal of Plant Diseases and Protection, 2019)

Probing the effect of various lipids and polymer blends on clopidogrel encapsulated floating microcarriers - Saba Irshad; Ikram Ullah Khan; Syed Haroon Khalid; Sajid Asghar; Muhammad Irfan; Ikrima Khalid; Nadeem Sabir; Adnan Ali; Ahmad Nawaz Khan; Abid Mehmood Yousaf; Talib Hussain; Yasser Shahzad (DARU Journal of Pharmaceutical Sciences, 2019)

Moderating role of financial development in environmental Kuznets: a case study of Malaysia - Abid Rashid Gill; Sallahuddin Hassan; Muhammad Haseeb (Environmental Science and Pollution Research, 2019)

Long-term ENSO relationship to precipitation and storm frequency over western Himalaya–Karakoram–Hindukush region during the winter season - Shahzad Kamil; Mansour Almazroui; In-Sik Kang; Muhammad Hanif; Fred Kucharski; Muhammad Adnan Abid; Fahad Saeed (Climate Dynamics, 2019)

Different nitrogen and biochar sources’ application in an alkaline calcareous soil improved the maize yield and soil nitrogen retention - Muhammad Farooq Qayyum; Mehak Ameer Abdullah; Muhammad Rizwan; Ghulam Haider; Muhammad Arif Ali; Muhammad Zafar-ul-Hye; Muhammad Abid (Arabian Journal of Geosciences, 2019)

Knockdown of the chitin-binding protein family gene CaChiIV1 increased sensitivity to Phytophthora capsici and drought stress in pepper plants - Muhammad Ali; Wen-Xian Gai; Abdul Mateen Khattak; Abid Khan; Saeed Ul Haq; Xiao Ma; Ai-Min Wei; Izhar Muhammad; Ibadullah Jan; Zhen-Hui Gong (Molecular Genetics and Genomics, 2019)

Composted Sugarcane By-product Press Mud Cake Supports Wheat Growth and Improves Soil Properties - Muhammad Umer Chattha; Muhammad Umair Hassan; Lorenzo Barbanti; Muhammad Bilal Chattha; Imran Khan; Muhammad Usman; Abid Ali; Muhammad Nawaz (International Journal of Plant Production, 2019)

Tamboti wood ash and burnt goat dropping ash, safe alternatives to control cowpea weevils, Callosobruchus maculatus (Fabr.) (Coleoptera: Bruchidae) during storage for subsistence farming - Bamphitlhi Tiroeselea; Gopolang Ranthoakgalea; Muhammad Irfan Ullah; Naunain Mehmood; Syed Muhammad Ali Zahid; Bushra Abid (Environmental Monitoring and Assessment, 2019)

Modeling predictive assessment of wind energy potential as a power generation sources at some selected locations in Pakistan - Muhammad Abid Khan; Hüseyin Çamur; Youssef Kassem (Modeling Earth Systems and Environment, 2019)

Arsenic fractionation and its impact on physiological behavior of sunflower (Helianthus annuus L.) in three texturally different soils under alkaline calcareous conditions - Muhammad Awais Piracha; Muhammad Ashraf; Abid Niaz (Environmental Science and Pollution Research, 2019)

Nickel toxicity in plants: reasons, toxic effects, tolerance mechanisms, and remediation possibilities—a review - Muhammad Umair Hassan; Muhammad Umer Chattha; Imran Khan; Muhammad Bilal Chattha; Muhammad Aamer; Muhammad Nawaz; Abid Ali; Muhammad Aman Ullah Khan; Tahir Abbas Khan (Environmental Science and Pollution Research, 2019)

Farmer Perceptions of Climate Change, Observed Trends and Adaptation of Agriculture in Pakistan - Muhammad Abid; Jürgen Scheffran; Uwe A. Schneider; Ehsan Elahi (Environmental Management, 2019)

Phytohormones enhanced drought tolerance in plants: a coping strategy - Abid Ullah; Hakim Manghwar; Muhammad Shaban; Aamir Hamid Khan; Adnan Akbar; Usman Ali; Ehsan Ali; Shah Fahad (Environmental Science and Pollution Research, 2018)

Flood hazards: household vulnerability and resilience in disaster-prone districts of Khyber Pakhtunkhwa province, Pakistan - Ashfaq Ahmad Shah; Jingzhong Ye; Muhammad Abid; Jahangir Khan; Syed Muhammad Amir (Natural Hazards, 2018)

Cascades of Ionic and Molecular Networks Involved in Expression of Genes Underpin Salinity Tolerance in Cotton - Muhammad Ali Abid; Chengzhen Liang; Waqas Malik; Zhigang Meng; Zhu Tao; Zhaoghong Meng; Javaria Ashraf; Sandui Guo; Rui Zhang (Journal of Plant Growth Regulation, 2018)

Management of tannery wastewater for improving growth attributes and reducing chromium uptake in spinach through citric acid application - Arosha Maqbool; Shafaqat Ali; Muhammad Rizwan; Wajid Ishaque; Nasir Rasool; Muhammad Zia ur Rehman; Arooj Bashir; Muhammad Abid; Longhua Wu (Environmental Science and Pollution Research, 2018)

Optimizing Irrigation Deficit of Multipurpose Cascade Reservoirs - Muhammad Usman Rashid; Abid Latif; Muhammad Azmat (Water Resources Management, 2018)

Regional climate assessment of precipitation and temperature in Southern Punjab (Pakistan) using SimCLIM climate model for different temporal scales - Asad Amin; Wajid Nasim; Muhammad Mubeen; Saleem Sarwar; Peter Urich; Ashfaq Ahmad; Aftab Wajid; Tasneem Khaliq; Fahd Rasul; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Hussani Mubarak; et al. (Theoretical and Applied Climatology, 2018)

Ellis–van Creveld syndrome and profound deafness resulted by sequence variants in the EVC / EVC2 and TMC1 genes - Muhammad Umair; Heide Seidel; Ishtiaq Ahmed; Asmat Ullah; Tobias B. Haack; Bader Alhaddad; Abid Jan; Afzal Rafique; Tim M. Strom; Farooq Ahmad; Thomas Meitinger; Wasim Ahmad (Journal of Genetics, 2017)

Effective Bioremediation of Endocrine-Disrupting Phthalate Esters, Mediated by Bacillus Strains - Muhammad Ali Surhio; Farah N. Talpur; Shafi M. Nizamani; Marvi Kanwal Talpur; Farah Amin; Abid Ali Khaskheli; Shazia Bhurgri; Hassan Imran Afridi; Shafiq Ur Rahman (Water, Air, & Soil Pollution, 2017)

Identification of novel potential genetic predictors of urothelial bladder carcinoma susceptibility in Pakistani population - Syeda Hafiza Benish Ali; Kashif Sardar Bangash; Abdur Rauf; Muhammad Younis; Khursheed Anwar; Raja Khurram; Muhammad Athar Khawaja; Maleeha Azam; Abid Ali Qureshi; Saeed Akhter; Lambertus A. Kiemeney; Raheel Qamar (Familial Cancer, 2017)

Pre-drought priming sustains grain development under post-anthesis drought stress by regulating the growth hormones in winter wheat (Triticum aestivum L.) - Muhammad Abid; Yuhang Shao; Sixi Liu; Feng Wang; Jingwen Gao; Dong Jiang; Zhongwei Tian; Tingbo Dai (Planta, 2017)

Biochar increased photosynthetic and accessory pigments in tomato (Solanum lycopersicum L.) plants by reducing cadmium concentration under various irrigation waters - Muhammad Abid; Subhan Danish; Muhammad Zafar-ul-Hye; Muhammad Shaaban; Muhammad Mutahir Iqbal; Abdur Rehim; Muhammad Farooq Qayyum; Muhammad Nadir Naqqash (Environmental Science and Pollution Research, 2017)

Foliar application of aspartic acid lowers cadmium uptake and Cd-induced oxidative stress in rice under Cd stress - Muhammad Rizwan; Shafaqat Ali; Muhammad Zaheer Akbar; Muhammad Bilal Shakoor; Abid Mahmood; Wajid Ishaque; Afzal Hussain (Environmental Science and Pollution Research, 2017)

Determinants of flood risk mitigation strategies at household level: a case of Khyber Pakhtunkhwa (KP) province, Pakistan - Ashfaq Ahmad Shah; Jingzhong Ye; Muhammad Abid; Raza Ullah (Natural Hazards, 2017)

Leaching of phthalate esters from different drinking stuffs and their subsequent biodegradation - Muhammad Ali Surhio; Farah N. Talpur; Shafi M. Nizamani; Marvi Kanwal Talpur; Hassan Imran Afridi; Abid Ali Khaskheli; Shazia Bhurgri; Junaid Ali Surhio (Environmental Science and Pollution Research, 2017)

The use of wastewater in livestock production and its socioeconomic and welfare implications - Ehsan Elahi; Muhammad Abid; Liqin Zhang; Gibson Maswayi Alugongo (Environmental Science and Pollution Research, 2017)

Rainfall Extremes: a Novel Modeling Approach for Regionalization - Muhammad Uzair Qamar; Muhammad Azmat; Muhammad Adnan Shahid; Daniele Ganora; Shakil Ahmad; Muhammad Jehanzeb Masud Cheema; Muhammad Abrar Faiz; Abid Sarwar; Muhammad Shafeeque; Muhammad Imran Khan (Water Resources Management, 2017)

Impact of Dysdercus koenigii Fabricius (Hemiptera: Pyrrhcoridae) density-dependent population on agronomic and qualitative characteristics of different transgenic cotton varieties - Muhammad Rafiq Shahid; Muhammad Farooq; Muhammad Shakeel; Abid Mahmood; Muhammad Dildar Gogi (Phytoparasitica, 2017)

Appraisal for site specific plant nutrient management through spatial variability and mapping in hilly areas of northern Pakistan - Munir Ahmad; Dost Muhammad; Maria Mussarat; Abid Ali Khan; Shah Faisal Khan; Muhammad Waqas Javed (Journal of Soils and Sediments, 2017)

Influence of ameliorating soil acidity with dolomite on the priming of soil C content and CO2 emission - Muhammad Shaaban; Lei Wu; Qi-an Peng; Lukas van Zwieten; Muhammad Afzal Chhajro; Yupeng Wu; Shan Lin; Muhammad Mahmood Ahmed; Muhammad Salman Khalid; Muhammad Abid; Ronggui Hu (Environmental Science and Pollution Research, 2017)

Direct and indirect effects of wastewater use and herd environment on the occurrence of animal diseases and animal health in Pakistan - Ehsan Elahi; Liqin Zhang; Muhammad Abid; Muhammad Tariq Javed; Han Xinru (Environmental Science and Pollution Research, 2017)

Transgenic expression of phytase in wheat endosperm increases bioavailability of iron and zinc in grains - Nabeela Abid; Asia Khatoon; Asma Maqbool; Muhammad Irfan; Aftab Bashir; Irsa Asif; Muhammad Shahid; Asma Saeed; Henrik Brinch-Pedersen; Kauser A. Malik (Transgenic Research, 2017)

Characterization of a salt resistant bacterial strain Proteus sp. NA6 capable of decolorizing reactive dyes in presence of multi-metal stress - Naila Abbas; Sabir Hussain; Farrukh Azeem; Tanvir Shahzad; Sajjad Haider Bhatti; Muhammad Imran; Zulfiqar Ahmad; Zahid Maqbool; Muhammad Abid (World Journal of Microbiology and Biotechnology, 2016)

Cotton production under risk: a simultaneous adoption of risk coping tools - Farhad Zulfiqar; Raza Ullah; Muhammad Abid; Abid Hussain (Natural Hazards, 2016)

Allelopathic potential of oil seed crops in production of crops: a review - Adnan Noor Shah; Javaid Iqbal; Abid Ullah; Guozheng Yang; Muhammad Yousaf; Shah Fahad; Mohsin Tanveer; Waseem Hassan; Shahbaz Atta Tung; Leishan Wang; Aziz Khan; Yingying Wu (Environmental Science and Pollution Research, 2016)

Effectiveness and benefit cost ratio of selected insecticides at different applicationon intervals for brinjal shoot and fruit borer, Leucinodes orbonalis (G.) management on brinjal, Solanum melongena (L.) at Sahiwal, Pakistan - Qudsia Yousafi; Muhammad Afzal; Muhammad Aslam; Allah Ditta Abid (Phytoparasitica, 2016)

Phenolic, flavonoid contents, anticholinesterase and antioxidant evaluation of Iris germanica var ; florentina - Farhat Ullah; Muhammad Ayaz; Abdul Sadiq; Abid Hussain; Sajjad Ahmad; Muhammad Imran; Anwar Zeb (Natural Product Research, 2016)

Use of RSM modeling for optimizing decolorization of simulated textile wastewater by Pseudomonas aeruginosa strain ZM130 capable of simultaneous removal of reactive dyes and hexavalent chromium - Zahid Maqbool; Sabir Hussain; Tanvir Ahmad; Habibullah Nadeem; Muhammad Imran; Azeem Khalid; Muhammad Abid; Fabrice Martin-Laurent (Environmental Science and Pollution Research, 2016)

Using PCA in evaluating event-controlling attributes of landsliding in the 2005 Kashmir earthquake region, NW Himalayas, Pakistan - Muhammad Basharat; Abid Ali; Ishtiaq A. K. Jadoon; Joachim Rohn (Natural Hazards, 2016)

Remediation of arsenic-contaminated water using agricultural wastes as biosorbents - Muhammad Bilal Shakoor; Nabeel Khan Niazi; Irshad Bibi; Ghulam Murtaza; Anitha Kunhikrishnan; Balaji Seshadri; Muhammad Shahid; Shafaqat Ali; Nanthi S. Bolan; Yong Sik Ok; Muhammad Abid; Fawad Ali (Critical Reviews in Environmental Science and Technology, 2016)

Prevalence and distribution of human Plasmodium infection in Federally Administrative Tribal Areas of Pakistan - Irfan Hussain; Naveeda Akhtar Qureshi; Muhammad Afzal; Nargis Shaheen; Abid Ali; Asma Ashraf (Acta Parasitologica, 2016)
About 3.6 million Pashtun and over 1.5 million immigrants from Afghanistan live in the federally administered tribal areas (FATA) on the border between Pakistan’s Khyber Pakhtunkhwa Province and southern Afghanistan. Although malaria cases are common in FATA, no detailed studies have yet been performed to reveal the actual status of malaria in the local population and epidemiological data are insufficient to elucidate the actual incidence. A malariometric survey of 691 patients of all ages and genders in seven agencies (districts) in FATA was carried out in 2013 using whole blood samples. Microscopically confirmed positive species were subjected to nested-PCR for the reconfirmation and detection of four species of

Effect of Beauveria bassiana infection on the feeding performance and antioxidant defence of red palm weevil, Rhynchophorus ferrugineus - Abid Hussain; Muhammad Rizwan-ul-Haq; Hassan Al-Ayedh; Sohail Ahmed; Ahmed Mohammed Al-Jabr (BioControl, 2015)

Effect of water deficit during vegetative growth periods on post-anthesis photosynthetic capacity and grain yield in winter wheat (Triticum aestivum L.) - Yakun Cui; Zhongwei Tian; Xu Zhang; Abid Muhammad; Huimin Han; Dong Jiang; Weixing Cao; Tingbo Dai (Acta Physiologiae Plantarum, 2015)

Optimization of Multiple Reservoirs Operation with Consideration to Sediment Evacuation - Muhammad Usman Rashid; Abdul Sattar Shakir; Noor Muhammad Khan; Abid Latif; Muhammad Mubashir Qureshi (Water Resources Management, 2015)

Diazotrophs-assisted phytoremediation of heavy metals: a novel approach - Abid Ullah; Hafsa Mushtaq; Hazrat Ali; Muhammad Farooq Hussain Munis; Muhammad Tariq Javed; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2015)

Synthesis, characterization antibacterial and antifungal activity of some transition metal complexes - Wajid Rehman; Zonera Hassan; Umer Rashid; Fazal Rahim; Obaid-Ur-Rahman Abid; Muhammad Waseem (Medicinal Chemistry Research, 2014)

Establishing midgut cell culture from Rhynchophorus ferrugineus (Olivier) and toxicity assessment against ten different insecticides - Ahmed Mohammed Aljabr; Muhammad Rizwan-ul-Haq; Abid Hussain; Abdullah I. Al-Mubarak; Hassan Y. AL-Ayied (In Vitro Cellular & Developmental Biology - Animal, 2014)

Correction for Irrelevant Absorption in Multicomponent Spectrophotometric Assay of Riboflavin, Formylmethylflavin, and Degradation Products: Kinetic Applications - Iqbal Ahmad; Kiran Qadeer; Kefi Iqbal; Sofia Ahmed; Muhammad Ali Sheraz; Syed Abid Ali; Tania Mirza; Ambreen Hafeez (AAPS PharmSciTech, 2013)

Application of the CSM-CERES-Rice model for evaluation of plant density and irrigation management of transplanted rice for an irrigated semiarid environment - Shakeel Ahmad; Ashfaq Ahmad; Hakoomat Ali; Abid Hussain; Axel Garcia y Garcia; Muhammad Azam Khan; Muhammad Zia-Ul-Haq; Mirza Hasanuzzaman; Gerrit Hoogenboom (Irrigation Science, 2013)

Measurement of radionuclides and absorbed dose rates in soil samples of Peshawar, Pakistan, using gamma ray spectrometry - Hasan M. Khan; Muhammad Ismail; Muhammad Abid Zia; Khalid Khan (Isotopes in Environmental and Health Studies, 2012)

Application of the CSM-CERES-Rice model for evaluation of plant density and nitrogen management of fine transplanted rice for an irrigated semiarid environment - Shakeel Ahmad; Ashfaq Ahmad; Cecilia Manuela Tojo Soler; Hakoomat Ali; Muhammad Zia-Ul-Haq; Jakarat Anothai; Abid Hussain; Gerrit Hoogenboom; Mirza Hasanuzzaman (Precision Agriculture, 2012)

Purification and Characterization of Novel α-Amylase from Bacillus subtilis KIBGE HAS - Saeeda Bano; Shah Ali Ul Qader; Afsheen Aman; Muhammad Noman Syed; Abid Azhar (AAPS PharmSciTech, 2011)

Prevalence of hepatitis C virus (HCV) genotypes in Balochistan - Sarwat Afridi; Muhammad Naeem; Abid Hussain; Naseebullah Kakar; Masroor Ellahi Babar; Jamil Ahmad (Molecular Biology Reports, 2009)

New insight in staphylococcin research: bacteriocin and/or bacteriocin-like inhibitory substance(s) produced by S. aureus AB188 - Sadia Saeed; Sheikh Ajaz Rasool; Samia Ahmed; Tanweer Khanum; Muhammad Bashir Khan; Atiya Abbasi; Syed Abid Ali (World Journal of Microbiology and Biotechnology, 2006)

New ceramides from Platytaenia multicaule - Viqar Uddin Ahmad; Muhammad Zubair; Muhammad Athar Abbasi; Farzana Kousar; Muhammad Abid Rashid; Nasir Rasool; Rasool Bukhsh Tareen (Natural Product Research, 2006)

Stochastic Goal Programming Model for Optimal Blending of Desalinated Water with Groundwater - Muhammad A. Al-Zahrani; Abid M. Ahmad (Water Resources Management, 2004)